Taux de change et commerce : étude de droit international - Pantoja, Marina (Université Paris 10, 2019)
La relation entre la monnaie et le commerce, et l’impact que le taux de change peut avoir sur le droit du commerce international suscitent de vives discussions. la charte de la havane préconisait la non-utilisation de la dévaluation du taux de change comme une arme commerciale. le gatt contient des articles qui s’adressent aux questions de change. cependant, la thématique suscite des polémiques concernant notamment l’applicabilité des accords de l’omc comme un remède commercial contre la dévaluation anti-compétitive de la monnaie. d’un autre côté, le fmi, institution créée dans le cadre de l’accord de bretton woods, est l’organe compétent pour traiter les questions internationales d’ordre financier, et l’article iv de son statut concerne en particulier son devoir de surveillance des politiques de change de ses états-membres, afin d’éviter l’obtention d’avantages anti-compétitifs par des moyens de change. les deux organisations sont censées travailler de manière conjointe pour accomplir les objectifs de la croissance économique globale, et c’est dans cette conception que l’harmonisation entre le droit de l’omc et les directives du fmi doit être mise en place, pour que l’objectif primordial d’atteindre la gouvernance globale pour le bien de tous devienne une réalité.
Keywords: Competencia; Competition law; Concurrence; Concurrence (droit); Cooperation among the WTO and the IMF; Coopération OMC et FMI; Droit commercial (droit international); Droit du commerce international; Droit international économique; Fonds monétaire international; Guerre commerciale; International Economic Law; International trade law; Manipulation des taux de change; Manipulation of exchange rates; Organisation mondiale du commerce; Taux de change (manipulation); Trade war

Le consentement étatique à la compétence des juridictions internationales - Marquet, Clément (Université de Genève, 2019)
Le consentement étatique à la compétence des juridictions internationales est un élément incontournable du droit international public. Il régit le le fonctionnement de la justice internationale. Cependant, malgré son ubiquité, la notion est mal comprise. Ce travail, à travers la jurisprudence de la CIJ, d'ITLOS, de l'OMC et du CIRDI, redéfinit ce consentement, à la lumière de son histoire, son rôle et ses enjeux. Cette re-contextualisation est accompagnée d'une présentation et d'une analyse des enjeux contemporains entourant la notion.
Keywords: Arbitrage; Arbitragem; Arbitration; CIJ; CIRDI; Compétence; Compétence de la compétence; Consentement; Cour internationale de justice; Droit international public; Forum prorogatum; ICSID; ITLOS; Interprétation; Investissements; Investments; Juridictions; MFN; NPF; OMC; Organisation mondiale du commerce; Recevabilité; TIDM

Le principe d’interprétation autonome dans la Convention de Vienne sur les contrats de vente internationale de marchandises - Boussofara, Anissa (Université Côte d'Azur, 2019)
L’étude de l’interprétation de la Convention des Nations Unies sur les contrats de vente internationale de marchandises du 11 avril 1980 (CVIM) révèle la nécessité de la mise en œuvre d’un principe d’interprétation autonome, également affirmé dans d’autres instruments juridiques (conventions onusiennes, Principes UNIDROIT). Le principe d’interprétation autonome, inhérent au droit transnational, impose la prise en compte du caractère international des normes à interpréter ainsi que la promotion de leur uniformité d’application. Il s’agit ainsi d’assurer l’autonomie des termes du texte juridique à interpréter. Le comblement des lacunes du texte, qui constitue le second versant de l’interprétation juridique, est opéré par le recours aux principes généraux sous-tendant le texte. Le recours aux règles de droit interne n’aura lieu qu’en dernier ressort. L’étude se propose d’évaluer la mise en œuvre du principe d’interprétation autonome lors de l’application de la CVIM. A cette fin, il convient d’observer l’attitude du juge français lors de l’application du texte, non sans examiner la jurisprudence internationale ainsi que les sentences arbitrales l’appliquant également. Certaines dispositions et expressions conventionnelles ont été privilégiées afin d’examiner leur interprétation (par exemple : le contrat de fourniture, la contravention essentielle, le raisonnable, l’article 78 imposant l’application d’intérêts à toute somme due sans en fixer le taux). Le principe de bonne foi, guidant l’interprétation de la CVIM est également décortiqué dans sa relation avec l’interprétation de la CVIM. Il ressort de l’étude que la jurisprudence française méconnait le principe d’interprétation autonome lors de l’application de la CVIM. La comparaison avec d’autres juridictions montre que certaines d’entre elles font état d’une meilleure considération des règles d’interprétation édictées dans la Convention (Allemagne, Italie). La jurisprudence arbitrale révèle des sentences particulièrement enclines à la mise en œuvre du principe d’interprétation autonome sans que cette pratique ne soit uniforme. Les arbitres du commerce international sont souvent dotés d’une culture internationaliste et surtout, ils ne relèvent d’aucun ordre juridique national. Ils sont par conséquent beaucoup moins susceptibles d’être influencés par des références de droit interne et ainsi plus à même d’opérer une interprétation autonome des textes internationaux qu’ils mettent en œuvre. Ceci étant, l’affirmation explicite de l’application d’un principe d’interprétation autonome est quasiment inexistante dans la jurisprudence arbitrale comme dans celle des tribunaux étatiques.La présente étude a pour ambition d’élargir la connaissance du principe d’interprétation autonome par les interprètes du droit matériel uniforme en utilisant la CVIM comme support de démonstration. Le rôle du principe d’interprétation autonome sera fondamental dans l’expansion et la bonne application du droit uniforme. En effet, cette méthode d’interprétation est à même de respecter l’objectif du droit uniforme. When analyzing the United Nations Convention on Contracts for the International Sale of Goods adopted the 11 April 1980 (CISG), a principle of autonomous interpretation appears. This principle is stated in other legal texts (as United Nations conventions and UNIDROIT Principles). The principle of autonomous interpretation belongs to the transnational law and leads to take into account the international character of the legal provisions to be interpreted and to promote the uniformity of their application as “expressed” in the article 7 of the CISG. General principles underlying the CISG are used for gap-fillings which is the second side of legal interpretation. Using national laws is the ultimate resort.The principle of autonomous interpretation in the application of the CISG will be studied. For this purpose, judicial decisions and arbitral awards will be examined. Dispositions from the Convention have been chosen for their interpretation to be examined. The principle of good faith is also examined in its relation with the CISG interpretation. It will be observed that French case-law doesn’t acknowledge the principle of autonomous interpretation. Arbitral awards show a more important tendency to apply the principle of autonomous interpretation but there is no uniformity. The arbitrators in international trade have multicultural traditions and do not depend on a forum. Therefore they are less likely to be “influenced” by national “references” and so much more capable to interpret autonomously international dispositions. Nevertheless the “express” affirmation of a principle of autonomous interpretation is missing from arbitral awards and judicial decisions. This thesis aims to enlarge the acknowledgement of the principle of autonomous interpretation by the interpreters of uniform law using the CISG as a model. The function of the principle of autonomous interpretation will be fundamental to the expansion and to the correct application of uniform law. This method of interpretation is respectful of the objective of uniform law.
Keywords: Arbitrage; Arbitral Awards; Bonne foi (droit international); Commerce international; Contrats de vente internationale de marchandises; Convention des Nations unies; Droit international et droit interne; Droit transnational; France; Jurisprudence arbitrale; Lex mercatoria; Principe de bonne foi; The principle of good faith; Transnational law

Les manifestations juridiques et fiscales du protectionnisme de l'Union : essai sur un mode durable de régulation du libre-échange - Tran, Christophe (Université de Rennes 1, 2019)
Le droit de l’Union semble fondamentalement réticent à la résurgence du pendant antagoniste du libre-échange sous le vocable générique de protectionnisme. Pourtant, les manifestations juridiques et fiscales de ce protectionnisme de l’Union existent, variées en qualité et en intensité, et interpellent le juriste quant à la finalité poursuivie par l’entité souveraine qui le met en œuvre. Volonté de protection d’un intérêt propre et supérieur à l’intérieur de ses frontières ou volonté de domination du commerce international par le truchement d’instruments de défense mis au service d’une guerre commerciale, le protectionnisme peut-il être juridiquement fondé ou économiquement et politiquement opportun ? La combinaison est-elle possible ? De manière prospective, l’exigence de développement durable intégrée dans le droit de l’Union, dont la pertinence s’affirme à la lumière de la crise écologique, exhorte le juriste à penser le protectionnisme sous un angle durable dépassant la simple dimension économique. C’est à ces hypothèses, en contrariété assumée – mais nuancée – avec les libertés de circulation irriguant le droit de l’Union, que cette recherche est consacrée.
Keywords: Compétence; Défense commerciale commune; Exception protectionniste; Intérêt de l’Union; Libre-échange; Pays de l'Union européenne; Protectionnisme; Régulation durable; Souveraineté; Souveraineté européenne

Harmonização das Regras de Execução do Acordo de Mediação Comercial Internacional - Carvalho, David França Ribeiro de (Universidade de São Paulo, 2019)
O acordo mediado é aquele alcançado pelas partes como resultado de um procedimento de mediação. Diversamente das sentenças arbitrais estrangeiras, as quais gozam de um instrumento global para seu reconhecimento e execução, sob os auspícios da Convenção de Nova York, os acordos mediados transnacionais não possuem um instrumento harmonizado ou uniformizado que lhes conferem a mesma segurança. A mediação é um método de resolução de conflitos cada dia mais utilizado nas relações comerciais transnacionais e o resultado alcançado pelas partes precisa ser provido de maior reconhecimento e exequibilidade transnacional. Assim, são apresentadas algumas questões conceituais sobre o reconhecimento e a execução dos acordos mediados comerciais transnacionais para, na sequência, evidenciando o fenômeno da transnormatividade e pluralidade normativa, apresentar o arcabouço jurídico existente e seus limites no âmbito europeu com a Diretiva Europeia 2008/52/CE e transnacional, com a Lei Modelo da UNCITRAL sobre Conciliação Comercial Internacional de 2002. Essas normas reforçam a importância da elaboração de instrumentos que possam melhor assegurar o reconhecimento e a execução dos acordos mediados transnacionais. São apresentados e examinados argumentos sobre a necessidade e eventuais formas para o reconhecimento e execução dos acordos mediados transnacionais, proporcionando um melhor acesso à justiça. Ao final, são evidenciadas formas para a harmonização/uniformização e contextualizada a questão no âmbito do ordenamento jurídico brasileiro.
Keywords: Acordo mediado transnacional; Cross-border enforcement; Harmonization; Harmonização; International commercial mediation; MARD; Mediación; Mediation; Mediação; Mediação comercial internacional; Médiation; Reconhecimento e execução; Transnational mediated settlement agreement

Third Party’s Intellectual Property Rights And The Seller’s Liability Under The United Nations Convention On International Sale Of Goods (CISG) And The Sale Of Goods Act (SGA) - Kiraz, Serife E. (University of Leicester, 2019)
This thesis is a comparative analysis of the provisions on the seller’s duty to deliver the goods free from any third-party intellectual property rights (IPRs) under the United Nations Conventions on the International Sale of Goods (CISG) and the UK Sale of Goods Act 1979 (SGA). As a consequence of technological advancement, there has been an increased observance of the interaction between intellectual property rights (IPRs), which are intangible property rights, and tangible goods. As a result of this interaction, growing numbers of goods, which are either subject to IPRs as a whole or that possess an IP-protected component, have become subject to sales agreements. The circulation of the goods around the world increases the likelihood that third-party IPRs over the goods will be infringed. This risk of infringement also raises the possibility that the application of IP law remedies will prevent the buyer from reselling or using the goods in question. This study is concerned with the question of how the sale of goods is affected by third-party IPRs, and it proposes to undertake a comparative analysis of the provisions that determine the seller’s liability when third-party IPRs arise in relation to goods that are sold under the CISG and the SGA. It seeks to determine which instrument offers sufficient protection that will benefit the buyer. In attempting to reveal the sufficient protection, it also undertakes a comparative analysis of the remedies that are available to the buyer under the CISG and the SGA when third-party IPRs over the goods are raised. With regard to the widely acceptance of the CISG by 89 states, and the dominant role of English law in commercial law and its preference as a governing law to most contracts, it is aimed to determine the differences and similarities between the CISG and the SGA, and the practical consequences of their application to the contracts when third-party IPRs over the goods arise. The thesis will seek to determine if the text of the relevant CISG articles can be improved and will accordingly formulate proposals that work towards this outcome.

Article 6.8 and Annex II of the WTO agreement on antidumping - Persoz, Dimitri (European University Institute, 2019)
Article 6.8 of the Antidumping Agreement (AD) allows domestic investigating authorities to make determinations on the basis of the best information available (BIA) when any interested party does not cooperate during an antidumping investigation under the discipline of Annex II of the AD. Since its introduction, this provision has been the source of extensive and neverending litigation in front of both domestic investigating authorities and the Dispute Settlement Body. In this thesis, we research to what extent the findings of the Panels and the Appellate Body regarding Article 6.8 AD are consistent with the mandate set out in Articles 3.2, 11 DSU and 17.6 AD and to what extent they are reasonable from an economic perspective. To answer the first question, we first discuss Articles 3.2, 11 DSU and 17.6 AD to establish what is the mandate of the Panels and the Appellate Body under the Dispute Settlement Body. We then examine the findings of the Panels and the Appellate Body in the interpretation of the seven terms of Article 6.8 AD under the previously established mandate. To answer the second question, we summarize the latest developments in the economic theory of adjudication and litigation. We then discuss the findings of the Panels and the Appellate Body using this economic standard. In the conclusion, we compare the results of our analysis with current negotiations on Article 6.8 AD in the Doha Round framework and further discuss the opportunity to create a single united international investigating authority.

Règlement des différends relatifs à l'investissement dans le système de règlement des différends de l'Organisation Mondiale du Commerce (OMC) : Étude comparative entre l'arbitrage investisseur-Etat et les mécanismes de règlement des différends de l'OMC - Al Jehni, Rania (Université Paris-Est, 2018)
Les investisseurs étrangers dans les secteurs de services occupent une position particulière dans le droit économique international : ils sont couverts par des accords internationaux d'investissement ainsi que par des disciplines multilatérales sur le commerce des services. Contrairement à ce que la pratique actuelle suggère, les deux principales composantes du droit économique international, à savoir le droit commercial et le droit des investissements, fusionnent. Ils partagent non seulement des principes et des règles essentiellement équivalents, mais leurs disciplines s'appliquent également aux mêmes sujets et situations. Les accords internationaux d'investissement et les règles de l’OMC sur le commerce des services (disciplines de l'AGCS), bien que de nature très différente, présentent des principes communs qui favorisent l'investissement international dans les secteurs de services. En particulier, les deux ensembles d'accords consacrent des obligations de non-discrimination entre les investisseurs étrangers et nationaux dans les secteurs de services. Dans cette situation, les investisseurs étrangers profitent également des obligations que les deux ensembles d'instruments imposent aux États contractants. Ces instruments prévoient de solides mécanismes de règlement des différends en cas de violation de leurs obligations. Les investisseurs étrangers dans les secteurs de services peuvent donc avoir recours à deux mécanismes alternatifs de règlement des différends pour contester les mesures de leurs pays hôtes qui enfreignent les obligations internationales.L’OMC, contrairement au CIRDI, est beaucoup plus qu’un simple système de règlement des différends : l’OMC possède un élément institutionnel important qui a la capacité de fournir et d’appliquer les valeurs systémiques. Cette différence fondamentale entre le système de règlement des différends de l’OMC et d’arbitrage du CIRDI fournit une perspective analytique à travers laquelle l’étude évalue et compare la portée précise du chevauchement entre les disciplines du commerce et de l'investissement, ainsi que la capacité des parties privées à recourir à ces mécanismes de règlement des différends.Du point de vue méthodologique, deux approches sont concevables. Une analyse comparative et contextuelle : l'accent est mis sur les accords internationaux accordant la qualité pour les parties privées dans les procédures internationales de règlement des différends. L'attention est attirée sur le droit international du commerce et d'investissement, en comparant les principes, les règles et les mécanismes de règlement des différends du cadre de l'investissement international (y compris les accords qui définissent les relations d'investissement internationales) et le cadre d'investissement assez limité de l'OMC, principalement les dispositions pertinentes de l'AGCS. Une approche inductive, la jurisprudence est également pertinente. Un examen approfondi de la jurisprudence existante sur chaque sujet, afin de clarifier le sens de règles par ailleurs vagues et ambiguës et de répondre finalement à la question de savoir si les procédures de règlement des différends de l'OMC pourraient constituer une alternative valable pour le règlement des différends entre l'investisseur dans le secteur de services et l'État.
Keywords: CIRDI; Centre international pour le réglement des différends relatifs aux investissements; Commerce international; Différends; ICSID; Investissements; Investissements étrangers; Investment; Investments; OMC; Organisation mondiale du commerce; Réglementation; Settlement; WTO; Échanges internationaux de services

The defence of illegality in international investment arbitration : a hybrid model to address criminal conduct by the investor, at the crossroads between the culpability standard of criminal law and the separability doctrine of international commercial arbitration - Busco, Paolo (Sant'Anna School of Advanced Studies ; Université Paris 1, 2018)
Cette thèse analyse la question relative au cas où, dans l'arbitrage international en matière d'investissements, dont le but principal est l'application des normes visées à la protection des investisseurs, l’État défendeur soutient que l'investissement pour lequel la protection est demandée a été obtenu au moyen d'une forme de criminalité. Dans ce contexte, la défense de l'illégalité soulevée par les État dans les contentieux d'investissement est de plus en plus courante. Cette défense fonctionne selon le schéma suivant : un État hôte enfreint les dispositions de fond que le droit international accorde aux investissements effectués dans un pays étranger, par exemple en expropriant un investisseur étranger de son investissement sans indemnité. Dans le différend qui s'ensuit devant un tribunal arbitral d'investissement, l'État défendeur invoque l'illégalité commise par l'investisseur lors de la réalisation de l'investissement pour se défendre contre la procédure arbitrale intenté contre lui. Le but principal de cette étude est celui de démontrer que des considérations systématiques de nature strictement juridique, aussi bien que de politique juridique, exigent que la défense d'illégalité dans l'arbitrage d'investissement soit strictement restreinte et qu'un tribunal ne puisse décliner d'exercer sa compétence / juridiction que dans des cas exceptionnels. Cette étude aboutit à la conclusion d'après laquelle les tribunaux d'arbitrage devraient plutôt examiner au cas par cas au stade du fond l'ensemble des circonstances soumises devant lui et procéder à une mise en balance appropriée entre les comportements de l'investisseur et ceux de l'État hôte. This thesis addresses the question as to how an investment Tribunal is to react if, in the context of a case brought before it for breach of standards of protection of an investment, the respondent argues that the investment for which protection is sought has been secured by resorting to some form of criminality. Against this background, a defence by the Host State that has become increasingly common is the so-called Defence of Illegality. It operates on the basis of the following scheme : a Host State breaches the substantive provision that international law accord to investments made in a foreign Country, for instance by means of expropriating without compensation the investor's investment. In the ensuing dispute before an investment Tribunal, the defendant Host State raises the illegality committed by the investor in the making of the investment as defence against the breach of the substantive provisions on the protection of the investment, of which it is accused, to avoid responsibility. This thesis intends to demonstrate that both legal and policy consideration dictate that the Defence of Illegality in investment arbitration should be strictly curtailed and that a Tribunal should only decline to exercise its jurisdiction in exceptional cases. Rather, Tribunals should look at the entire set of circumstances at the merits stage and perform a proper balancing test between the conduct of the investor and the Host State.
Keywords: Admissibility and jurisdiction; Admissibilité; Approche comparée; Arbitrage; Arbitrage commercial; Arbitrage d'investissement; Arbitrage et crime; Arbitrage international; Arbitragem; Arbitration; Arbitration and crime; Clause de légalité; Clean hands doctrine; Commercial Arbitration; Comparative law; Compétence; Compétence juridictionnelle; Corruption; Defence of Illegality; Doctrine des mains propres; Défense d'illégalité; Investment arbitration; Investments

Insolvência transnacional: as contribuições que a lei modelo da UNCITRAL pode proporcionar para o Brasil - Becue, Sabrina Maria Fadel (Universidade de São Paulo, 2018)
O Brasil nem sempre permaneceu alheio ao debate sobre insolvência transnacional, porém desde 1973 carece de normativa específica. A lacuna da lei, no entanto, não impede que os casos cheguem ao Poder Judiciário. Nos últimos anos, o número de processos desta natureza aumentou de forma considerável e apesar de terem atingido certo consenso quanto à solução encontrada pelos tribunais, a fundamentação das decisões expõe a fragilidade do sistema e a necessidade de reforma legislativa. A prevalência da UNCITRAL entre as demais organizações internacionais e o limitado escopo e estrutura da Lei Modelo sobre Insolvência Transnacional, permitiram que este instrumento de Soft Law fosse aceito como o padrão normativo mais adequado e internacionalmente reconhecido. A Lei Modelo da UNCITRAL contribui para segurança jurídica e previsibilidade no comércio internacional, por meio da harmonização do procedimento de insolvência transnacional em países oriundos de diferentes tradições jurídicas - Civil Law e Common Law - e que estão em diferentes estágios de desenvolvimento. A harmonização se restringe a regras comuns para o reconhecimento de um processo estrangeiro, medidas de assistência e cooperação entre tribunais, sem, contudo, avançar em questões de direito material que, como sabido, são sensíveis e refletem políticas internas de cada Estado. Assim, uma das principais vantagens da Lei Modelo é promover a cooperação direta entre tribunais e com os representantes da insolvência, a fim de eliminar a dependência dos países no princípio de cortesia internacional ou concessão de exequatur aos procedimentos de homologação de sentença estrangeira ou carta rogatória. Apesar dos benefícios proporcionados pela Lei Modelo, muitos países resistem a sua adoção e, entre aqueles que a incorporaram, há diversidade na sua interpretação e aplicação, o que pode colocar em risco o objetivo de harmonização. A fratura entre o texto da lei e sua prática foi objeto da investigação. Inobstante, o Brasil poderia se beneficiar da adoção da Lei Modelo da UNCITRAL, tanto para ampliar os meios de cooperação jurídica internacional, como para promover uma solução estável aos processos transnacionais. Contudo, é preciso entender o alcance deste instrumento e, via de consequência, suas limitações enquanto norma regente, uma vez que as contribuições esperadas da Lei Modelo estão proporcionalmente vinculadas aos seus restritos escopos. A tese questiona, por fim, se existe um sistema internacional de insolvência transnacional fundado no universalismo modificado ou qual o papel que pode ser atribuído a este na solução dos processos judiciais. Brazil has not always been disconnected from the debate on transnational insolvency, but since 1973 it lacks specific regulations. The gap in legislation, however, does not prevent cases from reaching the courts. In recent years, the number of cases of this nature has increased considerably and although some consensus has been reached on the solution found by the courts, the reasoning of the rulings exposes the fragility of the system and the need for legislative reform. The predominance of UNCITRAL in relation to other international organizations and the limited scope and structure of the Model Law on Transnational Insolvency allowed this Soft Law instrument to be accepted as the most appropriate and as an internationally recognized standard of cross-border regulation. The UNCITRAL Model Law contributes to legal certainty and predictability in the international trade by harmonizing the transnational insolvency proceedings in countries from different legal systems - Civil Law and Common Law - that are at different stages of development. Legal harmonization is restricted to common rules for the recognition of a foreign proceeding, assistance and cooperation between courts, without, however, advancing in matters of substantive law which, as it is well known, are sensitive and reflect public policies of each State. Thus, one of the main advantages of the Model Law is to promote direct cooperation between courts and insolvency representatives in order to eliminate the countries' reliance on international courtesy or the granting of exequatur to the procedures for ratification of a foreign judgment or letters rogatory. Despite the benefits provided by the Model Law, many countries resist their adoption, and among those who incorporate it, there is diversity in their interpretation and application, which may jeopardize the goal of harmonization. The fracture between the law on the books and its practice was the object of this investigation. In spite of this, Brazil could benefit from the adoption of the UNCITRAL Model Law, both to expand the means of international judicial cooperation and to promote a stable solution to transnational processes. However, it is necessary to understand the scope of this instrument and, consequently, its limitations as a governing norm, since the expected contributions of the Model Law are proportionally linked to its restricted scopes. The thesis finally poses the question of whether there is an international system of transnational insolvency based on the modified universalism or the role that can be attributed to it in the resolution of legal proceedings.
Keywords: Cooperação internacional; Cross-border Insolvency; Direito Internacional; Insolvência; Judicial Cooperation; Modified Universalism; Sentença estrangeira

Impacts de l'orientation entrepreneuriale sur la performance-export des PME Togolaises à vocation internationale. - Kombate, Kangnaguidjoa (Université du Littoral Côte d'Opale, 2018)
L'objectif de cette recherche est d'évaluer l'impact du profil du dirigeant sur le niveau d'OE et l'influence de ce dernier sur la performance-export de la PME dans le contexte togolais. A cet effet, une analyse quantitative par la période de régression logistique auprès de 65 PME exportatrices montre que la vision stratégique, les compétences clés, les traits de personnalité du dirigeant et les caractéristiques de la PME affectent positivement l’orientation entrepreneuriale internationale et la performance-export. Ces résultats ont le mérite de confirmer le modèle conceptuel adapté de Miller/Friesen et celui de Covin/Slevin dans le cadre du Togo. The objective of this research is to assess the impact of the CEO's profile on the EO level and its influence on the export performance of the SMBs in the togolese context. The results of a quantitative analysis by logistic regression led to 65 exporting SMBs to this purpose, show that the strategic vision, the key competences, the CEO's traits of personality and the SMBs characteristics, are positively related to to the international entrepreneurial orientation (IEO) and to the export performance. These results have the merit of confirming the conceptual model adapted from M/F and the one of C/S within the Togolese framework.
Keywords: CEO; Entrepreneuriat; Export-performance; International Entrepreneurial Orientation; Internationalisation; Internationalization; Orientation Entrepreneuriale Internationale; PME; Performance-export; Petites et moyennes entreprises; Propriétaire-dirigeant; SMB

O direito regulatório internacional e a obrigação de compensar e liquidar derivativos de balcão por meio de contraparte central: da uniformização internacional à harmonização local no mercado financeiro global - Padilha, Alexandre Garcia (Universidade de São Paulo, 2018)
O direito regulatório internacional tem papel central no desenvolvimento da obrigatoriedade de uso de contraparte central na compensação e liquidação de ativos financeiros, com especial referência aos derivativos registrados e negociados em mercados de balcão. Foi o direito regulatório internacional que ditou as regras a serem utilizadas pelas jurisdições de cada país ou região considerados relevantes para esse mercado, como Brasil, Estados Unidos da América, União Europeia e Austrália. O primeiro capítulo descreve, no âmbito internacional, o contexto em que o direito regulatório internacional passou a ser criado para ditar a formulação da referida obrigação. O segundo capítulo apresenta uma descrição do mercado de derivativos de balcão e suas características, que geraram a necessidade de atuação da regulação internacional. O terceiro capítulo descreve e analisa a inserção do Brasil nesse contexto regulatório internacional, que cria uma obrigação de utilização de contraparte central para compensar e liquidar obrigações do mercado de derivativos de balcão, apresentando assim uma nova perspectiva de análise para o mercado que, aparentemente, se chama local, mas que, cada vez, mais apresenta características globais. Nesse mesmo sentido, o quarto capítulo descreve a legislação da União Europeia no que se refere especificamente ao tema proposto e o quinto capítulo se dedica às regras norteamericanas. O sexto capítulo traz a recente reforma da legislação australiana para o mercado de derivativos, abarcando a obrigação de uso de contraparte central numa das últimas nações a implementar recomendações e princípios impostos aos membros do G20 em 2009 sobre a obrigação de utilização de contraparte central. O sétimo capítulo traz os pontos que se destacam em relação à comparação entre as quatro jurisdições estudadas, especificamente no que se refere aos conceitos utilizados e aos efeitos de cada uma das jurisdições para o contexto regulatório internacional. O oitavo e último capítulo traz uma análise crítica sobre o direito regulatório internacional exposto e as jurisdições nacionais e regionais estudadas comparativamente nos capítulos anteriores da tese. Ao final, estão as conclusões deste trabalho, voltadas para o reconhecimento da existência de um esforço cooperativo internacional em reestabelecer a estabilidade e solidez do sistema financeiro internacional e o crescimento econômico mundial, que surgiu após um momento de crise financeira, o que se deu, por exemplo, como se apresenta nessa tese, por meio da imposição de regras para participantes do mercado de balcão, onde sua atuação era considerada livre e praticamente sem supervisão ou fiscalização regulatória, especialmente em países como os Estados Unidos da América. A criação da obrigação de utilização de contraparte central que assegure o cumprimento das obrigações decorrentes de operações de derivativos de balcão foi implementada por meio de uma mobilização mundial para alcançar: (i) uniformização de princípios, recomendações, regras e condutas relacionadas ao tema no âmbito de um direito regulatório internacional reformulado; e (ii) harmonização dos arcabouços jurídicos regulatórios nacionais, com o fim de que todos sejam considerados equivalentes sobre esse tema.
Keywords: Central counterparty (CCP); Comércio internacional; Derivatives; Derivativos; International regulation; Over-thecounter (OTC) market; Sistema financeiro; Tratados internacionais

دور عملية تحويل الفواتير في تنمية التجارة الدولية - ماديو, ليلى (جامعة مولود معمري, 2018)
تقوم عمليّة تحويل الفواتير على تحويل حقوق من مالكها إلى مؤسّسة ماليّة متخصّصة (وسيط)، التي تتكفّل بتحصيل هذه الحقوق، في إطار عقد، مع تحمّل الخسائر المحتملة الناتجة عن إعسار المدينين. وعندما تكتسي هذه العملية الطابع الدّولي، تظهر صعوبات مرتبطة بالشكوك التي تدور حول القانون واجب التطبيق، والتي من شأنها عرقلة تطوّر العمليّة ذات الأهميّة البالغة في التجارة الدّوليّة، من هنا، تظهر أهميّة تبنّي قواعد موحّدة لتنظيم عمليّة تحويل الفواتير الدّوليّة. ومهما كان القانون واجب التطبيق على عمليّة تحويل الفواتير الدّوليّة، فإنّها تساهم في تنمية التجارة الدّوليّة بفضل تدخّل الشركات المتخصّصة فيها وتنظيمها في شكل سلاسل لتشجيع المؤسسات الصغيرة والمتوسطة على القيام بعمليات التصدير، خاصّة وأنّ هذه الأخيرة معرّضة للأخطار المرتبطة بالتجارة الدّوليّة، وبفضل الخدمات التي تؤديها العمليّة، ألا وهي تمويل الصادرات وضمانها L’affacturage est une technique qui consiste à céder des créances à un établissement de crédit spécialisé (le factor), qui prend en charge le recouvrement de ces créances dans le cadre d’un contrat, en supportant les pertes éventuelles sur les débiteurs insolvables. Et lorsque de telles opérations sont conduites au niveau international, surgissent des difficultés liées à l’incertitude juridique pouvant entraver l’essor de cette opération fort utile dans le commerce international, d’où l’utilité d’adopter des règles uniformes destinées à régir les opérations d’affacturage international. Mais quelque soit la loi applicable à l’affacturage international, celui-ci contribue au développement du commerce international grâce à l’intervention des factors qui s’organisent sous forme de chaines pour encourager les PME à exporter, surtout que ces dernières sont confrontées aux risques liés au commerce international, et grâce aux services que fournit l’opération, en l’occurrence; le financement et la garantie des exportations.
Keywords: Commerce international; Convention d'Ottawa; Financement des exportations; Garantie des exportations; Sociétés de transfert de factures; Transfert de droits; Transfert international de factures; اتفاقية أوتاوا; تحويل الفواتير الدّوليّة; تمويل وضمان الصادرات; تنمية التجارة الدولية; حوالة الحق في التجارة الدّوليّة; شركات تحويل الفواتير

Théorie des risques et transfert de propriété : comparaison des droits français, de l'OHADA et du commerce international - Ndordji, Allatan (Université de Poitiers, 2018)
La théorie des risques est un contenant dont le contenu est constitué des maximes d'origine romaine, imaginées pour caractériser les conséquences juridiques de l'inexécution de l'obligation contractuelle due à la survenance de l'événement de force majeure. Suivant ces maximes dénommées en latin res perit debitori, res perit creditori et res perit domino, les conséquences préjudiciables de l'inexécution de l'obligation sont supportées, soit par le débiteur de cette obligation, soit par son créancier, ou par la personne à laquelle appartient la chose, objet de cette obligation, fortuitement détruite.Un regard comparatif sur les droits positif français, de l'OHADA et la Convention de Vienne du 11 avril 1980 sur la vente internationale de marchandises, révèle la dominance de la règle res perit domino dans la conception de la résolution de la question des risques. Cette conception donne lieu à deux typologies de solutions de la charge des risques : l'application d'une règle considérée comme un principe consiste à libérer les contractants de leurs obligations réciproques en raison de l'inexécution fortuite d'une obligation ; un autre type de règles est consacré à des hypothèses dans lesquelles une seule partie contractante est déclarée libérée. L'examen de ces deux typologies de solutions révèle une redondance dans leur coexistence, et particulièrement flagrante dans les systèmes de l'OHADA et de la Convention de Vienne du 11 avril 1980. Les règles considérées comme dérogatoires constituent une simple reprise a contrario du principe. Cette redondance s'avère la conséquence de la même conception de la résolution de la question des risques dans les trois systèmes juridiques. Les solutions de la charge des risques sont réputées, dans l'opinion répandue, différentes suivant ces trois systèmes juridiques ; mais cette différence ne tient qu'à leur apparence. À les examiner de près, leur similitude est surprenante ; ces solutions découlent de la même conception et sont susceptibles des mêmes critiques. Parmi les trois maximes latines, on observe une nette dominance de la réception de la règle res perit domino : les risques pèsent sur la personne à laquelle la chose appartient au moment de sa perte. La règle consistant dans l'association des risques au transfert de la propriété s'observe de façon générale dans les trois systèmes juridiques. Cette conception du traitement de la question des risques a tendance à générer des règles inappropriées. Elle se répand à partir du droit positif français résultant de l'analyse dominante de certaines dispositions du Code civil de 1804, dont l'exactitude doit être éprouvée. Cette thèse présente le modèle incompris de ce Code, après une présentation des différentes solutions issues des trois systèmes juridiques ; elle invite par conséquent à restaurer la vision des codificateurs, porteuse des solutions naturelles, appropriées à la question des risques. La thèse met en évidence la relation entre la charge des risques et l'obligation de délivrance dans le système du Code civil de 1804. Elle démontre la finalité du mécanisme de transfert solo consensu de la propriété, laquelle ne consiste nullement à attribuer les risques l'acquéreur. La règle res perit domino n'existe pas en réalité dans le Code civil de 1804. Ce Code fait référence à la règle res perit debitori pour caractériser l'hypothèse dans laquelle la perte fortuite de la chose libère les contractants de leurs obligations réciproques. On y rencontre également la règle res perit creditori, mais qui diffère, du point de vue de son fondement, de celle issue du droit romain. Il convient de promouvoir les solutions naturelles incomprises du Code civil de 1804, dont l'analyse est renouvelée dans cette thèse. Le système de ce Code ignore la règle res perit domino ; celle-ci n'y est entrée en réalité que par l'Ordonnance n° 2016-131 du 10 février 2016 portant réforme du droit des contrats, du régime général et de la preuve des obligations.
Keywords: Conservation; Contract; Contrat; Convention de Vienne; Delivery; Délivrance; Obligation; Property; Propriété; Transfer; Transfert (droit); Vienna Convention

The Seller's right to cure under article 48 United Nations Convention on contracts for the international sale of goods - Mirambell i Fargas, Miquel (Universitat Pompeu Fabra, 2017)
In principle, contracts are enforceable mutually beneficial agreements. In the event of a breach of contract, many national, supranational, and international legal systems—as well as recent European harmonization projects on private law—turn to cure regimes for the furtherance of such (assumed) contractually generated welfare. Namely, a mandatory Nachfrist-mechanism, a hierarchy of remedies, and debtor’s (in sales law: seller’s) rights to cure—before and after performance date—are normative devices intended to perform and preserve contracts, employing purportedly better, more cost-effective remedies for breach. Discussion of the utility of these legal institutions undisputedly belongs to the debate on modern contract law. In this thesis, one of these cure-oriented devices is exhaustively analyzed: the seller’s right to cure after performance date under Article 48 CISG1. Whereas according to paragraph (1) the seller—provided that certain preconditions are met—can impose subsequent performance on the aggrieved buyer, under paragraphs (2-4) they can merely offer cure within a period of time, irrespective of any preconditions. Article 48 CISG’s systematic setting, comparative law framework, origin, forerunners, preconditions for existence—general and specific—performance in practice, legal consequences—with regards to both the breach-of-contract regime and the availability of other remedies under the CISG—, and economic-behavioural implications are exegetically analysed. A particular focus is given to the allocation of contractual risk (see epigraph 3.2.9). Finally, conclusions are drawn at two levels: one concerning the CISG’s regime and another related to general Contract law. En principio, los contratos son acuerdos ejecutables mutuamente beneficiosos. En caso de incumplimiento del contrato, muchos sistemas jurídicos nacionales, supranacionales e internacionales—así como los recientes proyectos europeos de armonización en derecho privado—recurren a regímenes de subsanación para promover el bienestar que presumiblemente se ha generado con el contrato. A saber, un mecanismo de un Nachfrist obligatorio, una jerarquía de remedios y derechos del deudor (en compraventa: del vendedor) de subsanar—antes y después de la fecha de cumplimiento—son instrumentos normativos destinados a dar cumplimiento a los contratos y a preservarlos por medio de remedios, a priori, económicamente más eficientes. La discusión sobre la bondad y utilidad de estas instituciones indudablemente pertenece al planteamiento de un derecho de contratos moderno. En esta tesis se analiza exhaustivamente uno de estos instrumentos de subsanación: el derecho del vendedor a subsanar después de la fecha de entrega en virtud del artículo 48 CISG2. Mientras que de acuerdo con su párrafo (1) el vendedor –reuniendo ciertas condiciones previas– puede imponer una ulterior ejecución al comprador perjudicado; en virtud de los párrafos (2-4), éste solamente puede ofrecer una subsanación dentro de un plazo, pero independientemente de cualquier condición previa. Del citado artículo 48 se analizan exegéticamente el entorno sistemático, el marco en derecho comparado, el origen, los precursores, las condiciones previas para la existencia—generales y específicas—, su ejecución en la práctica, las consecuencias jurídicas—en el régimen del incumplimiento del contrato y en la disponibilidad de otros remedios bajo la Convención—así como las implicaciones económicas y conductuales. Se hace una contribución en relación con la asignación del riesgo contractual (véase infra 3.2.9). Finalmente, se extraen conclusiones a dos niveles: uno enfocado al régimen de la Convención y otro relativo al Derecho de contratos en general.
Keywords: Artículo 48 CISG2; CISG; Derecho del vendedor; Seller's right

Regional trade integration and co-operation in Southern Africa : the case of the Southern African Development Community (SADC) - Mathebe, Mpubane Mox (University of South Africa, 2017)
Mercantile Law
Keywords: Economic integration; Foreign economic relations; Foreign trade regulation; Free Trade; Monetary unions; SADC; Southern African Development Community

Previsibilidade do dano contratual como critério limitador de responsabilidade no Direito do Comércio Internacional - Barros, Vera Cecilia Monteiro de (Universidade de São Paulo, 2017)
O objetivo central desta tese é avaliar se a regra da previsibilidade do dano contratual ressarcível é um método eficaz de limitação dos danos e se atende às exigências modernas do Comércio Internacional. Para o perfeito enquadramento e contextualização do tema central deste estudo, apresenta-se inicialmente a origem histórica do critério da previsibilidade do dano no campo da responsabilidade contratual, e faz-se uma análise do alcance do princípio da reparação integral do dano e do princípio geral de ressarcimento de dano no Direito romano. Em seguida, realiza-se um breve exame do Direito Contratual na França até o século XVI, bem como uma análise do ressarcimento do dano nas obras de Dumoulin, Domat e Pothier e, para encerrar a parte histórica, analisa-se o Código Civil francês e a obrigação de ressarcimento. Ato contínuo, adentra-se a fundo nas noções gerais e nuances da regra da previsibilidade do dano, verificando-se, inicialmente, o sentido geral da limitação. Em seguida, analisa-se a teoria do fim tutelado pelo contrato e os fundamentos (contratual e econômico) do critério da previsibilidade. Feito isso, são avaliados o objeto e o momento da previsibilidade e, após, a (não) limitação de responsabilidade ao devedor doloso. Na sequência, estuda-se a adoção da previsibilidade do dano contratual como critério limitador do ressarcimento nos sistemas domésticos e em alguns dos principais instrumentos internacionais de uniformização do direito europeu, quais sejam, nos Princípios de Direito Europeu dos Contratos (PECL), no Draft Common Frame of Reference (DCFR), no Common European Sales Law (CESL) e no Projeto do Código Europeu dos Contratos. Em seguida analisa-se dois dos principais instrumentos de harmonização normativa do Comércio Internacional: os princípios do International Institute for the Unification of Private Law (Unidroit) e, mais profundamente, a Convenção das Nações Unidas sobre Contratos de Compra e Venda Internacional de Mercadorias (CISG), que hoje é referência normativa para os contratos internacionais entre signatários, os quais representam dois terços do comércio mundial. E, por fim, faz-se a análise econômica da regra da previsibilidade com o objetivo, primeiramente, de se verificar se, de fato, ela promove eficiência econômica e se a sua previsão influencia o comportamento das partes, incentivando a revelação de informações relevantes. E, na medida em que a previsibilidade do dano é um conceito jurídico indeterminado, cujo desafio da doutrina e especialmente da jurisprudência é dar a ele contornos mais concretos e objetivos, analisase decisões judiciais e arbitrais que aplicaram e interpretaram a regra da previsibilidade do dano no âmbito da CISG para, depois, avaliar, também mediante a análise econômica do Direito, a forma como o posicionamento de juízes e árbitros sobre a referida regra afeta os custos de transação dos negócios comerciais internacionais. The main purpose of the thesis herein is to evaluate if the foreseeability rule regarding refundable contractual damage is an effective method of damages limitation and whether it attends the modern International Trade requirements. For the perfect framing and contextualization of the central theme of this study, it is initially presented the historical origin of the damage foreseeability criteria in the field of contractual liability and an analysis is made of the scope of the principle of full compensation for damage and of the general principle of compensation in Roman Law. Then, a brief examination of the Contract Law in France until the sixteenth century is carried out, as well as an analysis of reparation of damages in the works of Dumoulin, Domat and Pothier and, to close the historical part, the French Civil Code and the obligation to make reparation are also analyzed. Subsequently, it goes deeper into the general notions and nuances of the foreseeability damage rule, initially finding the general meaning of the limitation. Next, we analyze the theory of the purpose protected by the contract and the fundamentals (contractual and economic) of the criteria of foreseeability. Later, the object and the moment of foreseeability are evaluated, as well as the (non) limitation of liability to the intentional debtor. Following, it is herein studied the adoption of foreseeability of contractual damage as a limiting criterion for reimbursement in domestic systems and in some of the main international instruments for the standardization of European law, namely in the European Contract Law Principles (ECLP), in the Draft Common Frame of Reference (DCFR), in Common European Sales Law (CESL) and in the Draft of the European Code of Contracts. Two main instruments of normative harmonization of international trade are discussed below: the principles of the International Institute for the Unification of Private Law (Unidroit) and, more profoundly, the United Nations Convention on Contracts for the International Sale of Goods (CISG), which is currently the normative reference for international contracts among signatories, which represent twothirds of world trade. Finally, the economic analysis of the foreseeability rule is carried out, initially, in order to verify whether it promotes economic efficiency and whether its prediction influences the behavior of the parties, encouraging the disclosure of relevant information. And insofar as the damage foreseeability is an indeterminate legal concept, whose challenge in the doctrine and especially the jurisprudence is to give it more concrete and objective outlines, we analyze judicial and arbitral decisions that applied and interpreted the rule of foreseeability within the scope of the CISG, in order to afterwards assess, also upon the economic analysis of the Law, how the position of judges and arbitrators on such rule affects the transaction costs of international business.
Keywords: CISG; Commerce international; Comércio internacional; Contract damage; Dano contratual; Direito Comercial Internacional; Foreseeability; International Trade; Liability; Limitation; Reparação do dano; Responsabilidade contratual

طرق تحديد القانون الواجب التطبيق على عقود التجارة الدولية - عيد, عبد الحفيظ (جامعة مولود معمري, 2017)
تظهر طرق تحديد القانون واجب التطبيق على عقود التجارة الدولية في كل من المنهج التنازعي الذي يقوم على قاعدة إسناد و المنهج المباشر الذي يقدم الحل للنزاع بطريقة مباشرة وذلك بتطبيق قواعد قانونية تهتم بتنظيم العلاقات التجارية ذات البعد الدولي والتي تعرف بقواعد التجارة الدولية . يعتبر المنهج التنازعي من أقدم مناهج التي عرفتها نظرية التنازع والتي عرفت تطورات تعكس الفكر الفلسفي والاقتصادي والقانوني الذي يتخلل كل مرحلة من هذا التطور إلى أن إستقر في الأخير مبدأ سلطان الإرادة على ضوؤه يتم تحديد قانون العقد الدولي . مع تطورات الحاصلة في التجارة الدولية خاصة بعد التطور العلمي والتكنلوجي وتطور وسائل النقل وظهور مجتمع خاص يمارس هذه التجارة، ظهرت الحاجة إلى تطبيق قواعد قانونية ذات مضمون عالمي تستوعب تعقيدات هذه العقود التي تجاوزت المفاهيم الكلاسيكية التي جاءت بها القوانين الداخلية التي صدرت لتنظيم العقود الداخلية . Les modes de détermination de la loi applicable aux contrats de commerce international Les modes de choix de la loi applicable sur les contrats de commerce international se dégagent à la fois de l’application de la méthode dite conflictuelle qui se base sur la règle du rattachement, et de la méthode dite directe qui propose une solution directe au litige et ce, en application des règles régissant les relations à caractère international. La méthode dite conflictuelle est la plus ancienne ; elle a connu plusieurs étapes dans son évolution qui ont caractérisées la pensée philosophique, économique et juridique, jusqu’à l’émergence du principe de l’autonomie de la volonté sur lequel se base le choix de la loi applicable sur le contrat international. L’évolution connue dans le commerce international notamment au plan scientifique et technologique, l’évolution des moyens de transport et l’apparition d’une société qui pratique ce commerce, a fait apparaitre le besoin de règles à vocation mondiale prenant en compte la complexité de ce type de contrats qui dépassent largement les concepts classiques liés aux contrats internes.
Keywords: Arbitrage commercial international; Contrats commerciaux internationaux; Loi applicable; Pouvoir de volonté; Règles d'attribution; التحكيم التجاري الدولي; القانون الواجب التطبيق; سلطان الإرادة; عقود التجارة الدولية; قواعد الإسناد

L'encadrement juridique de "Documents Transférables Électroniques" - Gamal Eldine, Nabil (Université de Montpellier, 2017)
L’intérêt de la présente recherche est d'étudier d’une manière générale les communications électroniques dans le commerce international, et puis à titre particulier d’interpeler les nouveaux défis qui relèveraient de l’utilisation des "documents transférables électroniques", en réfléchissant sur les différentes approches et les méthodes à adopter afin de remédier aux éventuelles déficiences technologiques, identifier puis combler les lacunes juridiques qui se révéler lors de ces échanges. Il s’agirait donc d’une enquête sur les questions juridiques liées à la création, à l’utilisation et à l’exécution du "document transférable électronique" ; il s’agit d’un terme crée par la CNUDCI, ce qui renvoie d’une manière générale à l’équivalent électronique d’un instrument transférable négociable ou d’un document titre. Nous identifions principalement les trois grands axes. Premièrement, la protection des données personnelles. Elle fait l’objet de plusieurs réformes législatives. La plus récente est le Règlement européen 2016/679 du 27 avril 2016 qui vise à promouvoir l’utilisation de l’outil informatique, tout en accordant la protection appropriée aux données à caractère personnel. Deuxièmement, l'exigence d’unicité d’un document transférable (« Garantie de singularité »). La garantie de l’unicité d’un document exige qu’il soit le seul qui existe ou bien, que toute copie soit clairement identifiable comme telle. Les conséquences éventuelles de la reproduction non autorisée de tout document transférable électronique donnant au porteur ou au bénéficiaire le droit de demander la remise de marchandises ou le paiement d’une somme d’argent rendent nécessaire l’élaboration de mécanismes pour garantir l’unicité de ces instruments. Troisièmement, la possession du ‘document transférable électronique’ et la notion de contrôle pour l’identification du porteur. Outre le traitement de la question de l’exigence de la singularité, la recherche d’un mécanisme fonctionnellement applicable et équivalent pour satisfaire à l’exigence de la possession matérielle du document papier constitue un défi majeur. Dans la plupart des modèles juridiques régissant les documents transférables électroniquement, la notion de “contrôle” d’un document électronique est utilisée en tant qu’équivalent fonctionnel de la possession ; cela signifie que la personne qui exerce le contrôle du document transférable électronique est considérée comme le porteur habilité à s’en prévaloir. Ces documents électroniques sont gérés par des prestataires de confiance qualifiés pour garantir leur sécurité. The interest of this research is to study in general, the electronic communications in an international context, and then to focus on the ongoing challenges that occur on the field of ''electronic transferable documents''; for this we shall perceive the methods that have been adopted for the purpose of using such documents, in order to prevent eventual technological deficiencies, identifying and filling the legal gaps revealed throughout our study of these new challenges.Therefore we shall comprehend and defy the legal boundaries, in order to create, use and transfer ''electronic transferable documents''. It is a pre-requisite to clearly identify the subject of this study, which is the term 'electronic transferable record, a concept created by UNCITRAL, which refers generally to ' Electronic equivalent of a transferable record (negotiable or non-negotiable) or a document of a legal right.We shall identify the three following main topics:I. The protection of personal data and privacy has been subject to several legislative reforms. The most recent one is the European Regulation 2016/679 dated April 27th, 2016. This reform aims to promote the use of the IT (Information Technology) tools, while granting the appropriate protection to the personal data. These electronic records are managed by qualified services providers.II. Requirement for uniqueness of the record (''Guarantee of uniqueness'')The guarantee of the uniqueness of the document is to ensure that there is only one possible holder and owner of that document, as in the case of paper document, and that any copy is clearly identifiable as such. As a result of an unauthorized reproduction of any electronic transferable record, any such holder or beneficiary shall have the right to request delivery of goods or the payment of a certain sum of money; thus the need to insure the uniqueness of these electronic records.III. The possession of an electronic transferable record.In addition to the above, the need to identify a functional equivalent approach to satisfy the requirement of possession in the case of electronic transferable document, which is a major challenge.IV. Concept of control and identification of the holderIn most legal models governing electronic transferable records, the definition of ''control'' of an electronic document is used as a functional equivalent to possession. That is, the person who controls the electronic transferable record is deemed to be the holder and the one entitled to use it.
Keywords: Bill of Exchange; Billet à ordre; Commerce électronique; Document transférable électronique; E-Commerce; Electronic signature; Gestion électronique de documents; Lettre de change; Promissory note; Signature électronique; Transferable records

Viyana satım sözleşmesi uyarınca teslim borcu - Davarci, Atakan Âdem (İstanbul Ticaret Üniversitesi, 2017)
CISG, yeknesak satım hukuku oluşturma çabasının bir sonucu olarak karşımıza çıkmaktadır. CISG'in temelini satım sözleşmesi oluşturur. Satım sözleşmesi insanların mal alımını sağlayarak ihtiyaçlarını karşılamasını sağlayan bir sözleşmedir. Satım hukukunun temelini satım sözleşmesi oluşturmaktadır. Satım sözleşmeleri tarafların mal ve satım bedeli üzerinde anlaşmaları ile kurulur. Satım sözleşmesinde satıcının asıl borcu ise sözleşmeye konu malın teslimidir. Malın doğru yer ve zamanda teslim edilmesi ve teslim edilen malın sözleşmeye uygun olması konuları teslimin en önemli unsurlarıdır. Malın sözleşmeye uygun olmaması veya sözleşmeye uygun yer ve zamanda teslim edilmemesi satıcının sözleşmeye aykırı davrandığını gösterir. Sözleşmeye aykırılığın tespiti, aykırılığın derecesine göre alıcıya bazı haklar tanımaktadır. Bu çalışma, hem teslim borcunun içeriğini hem de teslim borcu açısından sözleşmeye aykırılığı ayrıntılı olarak ele almaktadır. CISG emerges as a result of the effort to create a uniform selling law. The basis of the CISG is the contract of sale. The sale contract is a contract that allows people to buy goods and meet their needs. The sales contract constitutes the foundation of the law of sale. Sale contracts are established with the parties agreeing on the goods and sales price. The actual debt of the seller on the sales contract is the delivery of the goods subject to the contract. The fact that delivery at the right place and time and the delivered goods conform to the contract are the most important elements of delivery. The fact that the merchandise is incompatible with the contract or not delivered at the proper time and place indicates that the seller is breaching the contract. The determination of breach of contract gives the buyer some rights according to the degree of breach. This study elaborates on the contradiction to the contract in terms of both the content of the delivery debt and the delivery debt.
Keywords: CISG; Commercial law; Contracts; Milletlerarası Mal Satımlarına İlişkin Birleşmiş Milletler Antlaşması; Obligation to delivery; Sözleşmeler; Teslim borcu; Ticaret hukuku; Turkish commercial law; Türk ticaret hukuku; Vienna Sales Convention; Viyana Satım Sözleşmesi

Essai sur la définition d’un statut juridique de la procédure de dédouanement des envois postaux - Bedet, Florian (Université Paris-Saclay, 2016)
La thèse entreprise a pour objectif d’essayer de définir un statut juridique de la procédure de dédouanement des envois postaux. La nature juridique des envois postaux justifie un traitement douanier autonome et distinct des formalités douanières applicables aux marchandises des échanges commerciaux internationaux. Les travaux réalisés devraient tout d’abord aider à répondre aux problématiques liées aux difficultés juridiques de la définition de cette procédure de dédouanement spécifique et leurs conséquences. L’étude portera particulièrement sur le règlement des différends entre les autorités douanières et les importateurs ou exportateurs d’envois postaux internationaux en cas de litige lié au dédouanement. Au préalable, il faut donc relever et clarifier les règles juridiques qui sont déjà applicables au dédouanement des envois postaux, tant au niveau national et européen, qu'au niveau international en ce domaine. Cependant, cela se révèle difficile, et il faut rester opiniâtre devant l'extrême diversité des sources et des textes, parsemés dans de nombreuses branches du droit. Il faut ensuite nécessairement tenter de redéfinir, clairement et simplement, la notion d’envoi postal et la notion de service postal universel justifiant l'application d'une procédure spécifique de dédouanement des envois postaux. La notion de service postal universel implique un dédouanement rapide des envois postaux. Les administrations douanières ont, elles, l’obligation d’assurer le contrôle de toutes les marchandises importées ou exportées de leurs territoires nationales. La mission principale des autorités douanières est de protéger l’attractivité économique des Etats. Les agents douaniers doivent, d’une part, prélever les droits de douane et taxes à l’importation, d’autre part, lutter contre les trafics illicites de marchandises prohibées ou soumises à restriction. La délicate combinaison de l’universalisme du service postal et des obligations douanières doit permettre la reconnaissance et l’établissement d’une procédure de dédouanement spécifique aux envois postaux impliquant une nouvelle détermination des envois relevant du service postal universel et la mise en place de règles de dédouanement obligatoires et communes à l’ensemble des services postaux internationaux. La mise en œuvre d’une coopération internationale renforcée entre les services postaux et les autorités douanières est, en ce sens, préalablement indispensable. L’étude doit permettre de rendre compréhensible, pour les entreprises et les particuliers nationaux et européens, le droit positif douanier applicable au dédouanement postal. On analysera notamment les infractions et les règles douanières sanctionnant les diverses fraudes que l’on retrouve le plus fréquemment en pratique. L’essai sur la définition d'un statut juridique de la procédure de dédouanement des envois postaux démontrera qu’il est impératif de renforcer les pouvoirs et les moyens de contrôle et de sanctions des autorités douanières pour ce type singulier de dédouanement. Les voies de recours non-contentieuses et contentieuses qui sont ouvertes aux redevables et requérants feront également l’objet d’un traitement particulier. Les droits des redevables ou requérants sont notamment garantis par le principe de contrôle de la légalité des décisions de l’Administration des douanes et de ses agents par le juge judiciaire. Le juge judiciaire et le droit européen limitent et encadrent les pouvoirs exorbitants des autorités douanières.
Keywords: Commerce international; Contentieux douanier; Coopération; Coopération internationale; Droits de douane; Fraud; Fret; Litigation; Mailings; Postal customs clearance; Postes; Service postal universel; Taxes and customs duties; Taxes et droits de douane à l'importation; Universal postal service; Échanges commerciaux internationaux

Essai sur la définition d'un statut juridique de la procédure de dédouanement des envois postaux - Bedet, Florian (Université Paris-Saclay, 2016)
La thèse entreprise a pour objectif d’essayer de définir un statut juridique de la procédure de dédouanement des envois postaux. La nature juridique des envois postaux justifie un traitement douanier autonome et distinct des formalités douanières applicables aux marchandises des échanges commerciaux internationaux. Les travaux réalisés devraient tout d’abord aider à répondre aux problématiques liées aux difficultés juridiques de la définition de cette procédure de dédouanement spécifique et leurs conséquences. L’étude portera particulièrement sur le règlement des différends entre les autorités douanières et les importateurs ou exportateurs d’envois postaux internationaux en cas de litige lié au dédouanement. Au préalable, il faut donc relever et clarifier les règles juridiques qui sont déjà applicables au dédouanement des envois postaux, tant au niveau national et européen, qu'au niveau international en ce domaine. Cependant, cela se révèle difficile, et il faut rester opiniâtre devant l'extrême diversité des sources et des textes, parsemés dans de nombreuses branches du droit. Il faut ensuite nécessairement tenter de redéfinir, clairement et simplement, la notion d’envoi postal et la notion de service postal universel justifiant l'application d'une procédure spécifique de dédouanement des envois postaux. La notion de service postal universel implique un dédouanement rapide des envois postaux. Les administrations douanières ont, elles, l’obligation d’assurer le contrôle de toutes les marchandises importées ou exportées de leurs territoires nationales. La mission principale des autorités douanières est de protéger l’attractivité économique des Etats. Les agents douaniers doivent, d’une part, prélever les droits de douane et taxes à l’importation, d’autre part, lutter contre les trafics illicites de marchandises prohibées ou soumises à restriction. La délicate combinaison de l’universalisme du service postal et des obligations douanières doit permettre la reconnaissance et l’établissement d’une procédure de dédouanement spécifique aux envois postaux impliquant une nouvelle détermination des envois relevant du service postal universel et la mise en place de règles de dédouanement obligatoires et communes à l’ensemble des services postaux internationaux. La mise en œuvre d’une coopération internationale renforcée entre les services postaux et les autorités douanières est, en ce sens, préalablement indispensable. L’étude doit permettre de rendre compréhensible, pour les entreprises et les particuliers nationaux et européens, le droit positif douanier applicable au dédouanement postal. On analysera notamment les infractions et les règles douanières sanctionnant les diverses fraudes que l’on retrouve le plus fréquemment en pratique. L’essai sur la définition d'un statut juridique de la procédure de dédouanement des envois postaux démontrera qu’il est impératif de renforcer les pouvoirs et les moyens de contrôle et de sanctions des autorités douanières pour ce type singulier de dédouanement. Les voies de recours non-contentieuses et contentieuses qui sont ouvertes aux redevables et requérants feront également l’objet d’un traitement particulier. Les droits des redevables ou requérants sont notamment garantis par le principe de contrôle de la légalité des décisions de l’Administration des douanes et de ses agents par le juge judiciaire. Le juge judiciaire et le droit européen limitent et encadrent les pouvoirs exorbitants des autorités douanières.
Keywords: Commerce international; Contentieux douanier; Coopération; Coopération internationale; Droits de douane; Fraud; Fret; Litigation; Mailings; Postal customs clearance; Postes; Service postal universel; Taxes and customs duties; Taxes et droits de douane à l'importation; Universal postal service; Échanges commerciaux internationaux

The liability of trade unions for conduct of their members during industrial action - Mlungisi, Ernest Tenza (University of South Africa, 2016)
South Africa has been experiencing a number of violent strikes by trade unions in recent times. The issue is not only to hold unions liable for damage caused during strikes, but also to reduce the number of violent strikes. This study investigates if victims of such violence can hold trade unions liable for the violent acts committed by their members during industrial action. The Labour Relations Act, 66 of 1995 (LRA) makes provision for the dismissal of employees who commit misconduct during an unprotected strike. It also provides the remedy of an interdict and a claim for just and equitable compensation which can be made against the union, during an unprotected strike. It is further possible to hold the union together with its members liable for damages in terms of the Regulation of Gatherings Act, 205 of 1993 (RGA). The study argues that a strike or conduct in furtherance of a strike that becomes violent could lose protection and the trade union should consequently be held liable, in terms of the LRA and/ or the RGA, for damages caused by its members. This study investigates the position in Canada, Botswana and Australia to determine if there could be any other basis upon which to hold trade union liable for the conduct of its members. The study recommends that the common law doctrine of vicarious liability should be developed by the courts to allow trade unions to be held liable for damages caused by members during violent industrial action. Policy considerations and changing economic conditions and the nature of strikes in the Republic favours the expansion of the doctrine of vicarious liability to trade union member relationship.
Keywords: Common law; Industrial relations; Interest arbitration; Labor unions; Liability (Law); Secret ballot requirement; South Africa; Strikes and lockouts; Tort liability of labor unions; Trade union denial; Trade union liability

The timing of the passing of property and risk under the English Sale of Goods Act 1979, the CISG and the Libyan law: the interplay between the principle of party autonomy and the default rule - Aboukdir, Anwar (University of Stirling, 2016)
This thesis attempts to critically and comparatively analyse the issues relating to the passing of property and risk under the United Nations Convention on the Contract for International Sale of Goods (CISG) and English Law (SGA). The passing of property and risk plays a central role in the area of international legislation in relation to sales contracts. These elements can be the most significant components in contracts of sale between parties, whether in the international or domestic field. The reason is founded on their legal nature and the close relationship between them. The passing of property and risk has been a central issue for practitioners, judges and lawyers dating back to the Roman period and several ideas have been proposed to resolve it. Where the situation is different for contracts of sale in relation to the passing of property and risk, whether in the domestic or international field, it still creates many unresolved problems, because of ongoing changes in the field of modern commerce, which may contribute to unfair implications between the parties. It has been observed in this thesis that both English law and the CISG adopt the party autonomy principle, where the intention of the parties - whether in relation to the passing of property or risk - is the basic rule. However, the difference lies in the default rules. While English law involves default substitutional rules, which apply in cases where there is an absence of an expressed or implied indication regarding the intention between the parties, the CISG lacks such default rules regarding the transfer of property, which could be viewed as its main weakness, although the CISG does involve such provisions with respect to the transfer of risk. This thesis willdiscusses, the legal nature of the rules in relation to the passing of property and risk, and the role of the party autonomy principle, and the impacts and legal difficulties that might arise through the application of these rules, whether they are default rules or based on the party autonomy principle. It will also examine the legal gaps and weaknesses of both legal systems in an attempt to identify such legal difficulties and to find appropriate solutions and remedies.

Connectivité et accès au marché international : cas des pays de la Communauté économique monétaire de l'Afrique centrale (CEMAC) - Djam’Angai, Ludé (Université Cheikh Anta Diop, 2016)
Cette thèse a pour objectif général d 'analyser les effets de la connectivité sur l'accès au marché international des pays de la CEMAC. D'une part, elle expose les effets de la connectivité physique sur les échanges et, d'autre part, elle présente le rôle joué par les institutions dans la connectivité et la facilitation des échanges. En utilisant le modèle de gravité augmenté sur la période de 2006-2013 à partir de la méthode de Pseudo Maximum de Vraisemblance de la Loi de Poisson (PPML), les résultats d 'estimations économétriques ont pu montrer que la CEMAC reste un espace peu connecté et cette faible connectivité constitue un obstacle à ses échanges. De plus, afin de mener à bien notre régression, l'analyse en composante principale (ACP) a été utilisée pour calculer un indice de connectivité physique de transport, de démontrer l'hétérogénéité infrastructurelle et spatiale de la CEMAC, et de classer les pays les plus connectés de la zone.
Keywords: ACP; CEMAC; Connectivité; Marché international; Modèle de gravité

Commerce international et investissements directs étrangers : complémentarité ou substituabilité ? - Tayara, Saeed (Université de Poitiers, 2016)
Ce travail étudie, théoriquement et empiriquement, l'interaction entre le commerce international et l'investissement direct étranger (IDE), interaction qui a été un des principaux canaux de la mondialisation économique et de l'essor des chaînes de valeur mondiales dans la segmentation des activités de production. Les modèles théoriques montrent que le commerce international et les IDE peuvent se développer dans une relation de substituabilité ou de complémentarité. La nature de cette relation peut être la conséquence de facteurs exogènes, déterminants de la spécialisation des pays, ou le résultat de la stratégie endogène des firmes dans l'organisation de leurs activités à l'international. La validation empirique s'appuie sur une adaptation du modèle de gravité, en appliquant les techniques économétrique sur données de panel sur des données bilatérales pour la France au cours de la période de 1993 à 2012. Les estimations mettent en évidence une relation de complémentarité entre le commerce et l'IDE au niveau le plus agrégé. Cependant, une analyse comparative à un niveau plus désagrégé permet de trouver des indices de substituabilité et de complémentarité selon les groupes de pays partenaires.
Keywords: Commerce extérieur; Commerce international; Complementarity; Complémentarité; Données de panel; Entreprise multinationale; Entreprises multinationales; Foreign direct investment; Gravity model.; International Trade; Investissement étranger direct; Investissements étrangers; Modèle de gravité; Modèles économétriques; Multinational firm; Panel data; Substituabilité; Substitutability

A Convenção de Viena sobre contratos de compra e venda internacional de mercadorias e o papel do Estado no projeto de uniformização do Direito Privado Internacional - Bertotti, Daniela (Pontifícia Universidade Católica de São Paulo, 2016)
The present study aims at analyzing the United Nations Convention on Contracts for the International Sale of Goods (CISG) by examining most thoroughly the different interpretations of its text on the light of several western legal traditions. This analysis of the implications of such different interpretations will give rise to a discussion on the level of interpenetration among different legal systems. This, in turn, leads to an analysis of the impact of the conditions imposed by the Convention on its interpretation, which is considered a selfcontained autonomous ruling within the text of the Convention. As can be seen from a historical overview of the matter, the pursuit of unified regulations governing the international purchase and sale of goods is precisely the result of trade practices and of the consolidation of customary laws and principles. This thesis is thus based on the dynamics of this unifying process. The analysis will focus on its innovative feature of a consonant interpretation; an important structural element which may determine the success or failure of the text of the Convention when observed in different legal environments. It will be taken into consideration the role of the relation between governments and their institutions established with International Organizations, as well as that of the need for predictability when signing international agreements. Therefore, elements such as sovereignty and globalization are essential for a proper understanding of the impacts of this Convention in international law, namely, international trade laws
Keywords: CISG; Contracts; Contrato Internacional de Compra e Venda; Direito internacional privado; International Sales of Goods; Interpretation; Interpretação; United Nations Convention on Contracts

Transparency and dispute settlements : a study of the agreements on sanitary and phytosanitary measures and technical barriers to trade - Karttunen, Marianna (European University Institute, 2016)
Transparency of trade regulations by all WTO Members is essential for open, fair and predictable trade relations. Because of the negative integration process followed by the WTO Agreements, a myriad of different regulations apply in all WTO Members and have the potential of affecting international trade. With the progressive lowering of tariffs since 1947, these differing regulations remain the most significant barriers to trade, and the most difficult to reduce. The Agreements on Sanitary and Phytosanitary (SPS) measures and on Technical Barriers to Trade (TBT) provide the most comprehensive frameworks to address the costs arising from such regulatory diversity, through extensive obligations on regulatory transparency and cooperation and introducing elements of positive integration. Does transparency, within the SPS and TBT Agreements prevent disputes from rising, or ensure all Members access necessary information to raise more and better disputes? Through a presentation of the legal obligations and institutional framework of the two agreements (Part I), an in-depth analysis of the issues encountered by WTO Members in the implementation of the two Agreements and raised as trade concerns in the SPS and TBT Committees (Part II), and a study of the factors leading to disputes and transparency's role in addressing them (Part III), this thesis will demonstrate that transparency as it exists under the two agreements has the potential to both complement dispute settlement, by giving equal access to information for Members to raise disputes, and substitute dispute settlement, by fostering dialogue between Members before their frictions escalate to formal disputes. In this sense, the strength of the WTO legal and institutional system goes well beyond its dispute settlement system, with enforcement of WTO obligations fostered by better information sharing and dialogue among Members themselves, through non-judicial means.
Keywords: Food adulteration; Food inspection; Foreign trade regulation; Non-tariff trade barriers; Produce trade

OMC et droit de la concurrence : le droit de l'OMC face au défi de la mondialisation des pratiques anticoncurrentielles et des opérations de concentration - Ndiaye, Djibril (Aix-Marseille Université, 2015)
En tant qu’organisation qui a vocation à réguler les échanges commerciaux mondiaux et qui promeut le libre-échange, l’OMC désigne naturellement l’une des principales, voire l’unique, structure internationale capable d’incarner l’approche multilatérale qui s’impose devant la mondialisation des pratiques anticoncurrentielles et des opérations de concentration. Les règles de concurrence présentes dans son corpus juridique, ainsi que la jurisprudence issue de leur mise en œuvre, grâce notamment à l’existence d’un mécanisme contraignant de règlement des différends, forment un droit primaire de la concurrence. Toutefois, un tel droit ne régit que les comportements des acteurs étatiques et n’appréhende les agissements des particuliers que de manière indirecte. Par conséquent, il nécessite d’être complété et adapté aux nouvelles réalités procédant de la mondialisation des économies, ce par le biais d’une adoption d’un accord multilatéral portant sur la concurrence. Le système de règlement des litiges devrait aussi subir une mutation, en renforçant ses techniques de sanction et en s’ouvrant aux personnes privées
Keywords: Accord multilatéral; Anti-Competitive practices; Comity; Commerce international; Competencia; Competition law; Concurrence; Concurrence (droit); Courtoisie; Dispute settlement body; Droit et mondialisation; Extraterritoriality; Extraterritorialité; Globalization; Mondialisation économique; Multilateral agreement over the competition; OMC; Organe de règlement des différends; Organisation mondiale du commerce; Pratiques anticoncurrentielles; WTO

Les conflits d'intérêts en arbitrage commercial international - Castres Saint Martin, Constance (Université Paris 2, 2015)
Le conflit d'intérêts est un sujet passionnant notamment en raison de son omniprésence dans l'actualité. Approximative, l'expression empruntée au magma lexical des politiciens et juristes anglo-américains s'est récemment diffusée en France dans le monde des affaires et aussitôt reprise par le jargon médiatique pour désigner des éventuelles interférences de l'intérêt privé dans l'exercice de pouvoirs de nature privée ou publique. Il n'existe en l'état actuel du droit positif français aucune réglementation spécifique de ces « conflits d'intérêts », pas plus en droit privé qu'en droit public, alors même qu'on se préoccupe de leur prévention tandis que leur sanction relève de qualifications plus générales. Il convient donc de s'interroger sur la définition et la valeur opératoire de cette notion et le régime juridique qui pourrait lui être réservé, ce que l'on se propose d'entreprendre dans la sphère du droit privé et par préférence dans le champ de l'arbitrage commercial, particulièrement exposé aux appétits hégémoniques des droits anglo-américains. Conflict of Interests is a fascinated subject due to its pervasiveness in the economic life. This approximated expression, borrowed from the politicians and Anglo-American lawyers' jargon, has recently spread into the French business world and was taken up by the media to designate the interferences of private interest in the exercise of powers of private or public nature. In the current state of French Law, there is no specific rule governing conflicts of interests, neither in Private Law, nor in Public Law. Indeed, politicians and scholars paradoxically only focus on their prevention, whereas their sanctions fall within the scope of broader notions. The aim of this research is to lay down the definition, the operative value and the regime of conflict of interests. The scope of this research shall be, within Private Law, Commercial Arbitration Law, which is particularly exposed to the hegemony of Anglo-American laws.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitral abuses; Arbitration; Confiance légitime (droit); Confidence principle; Conflict of interests; Conflit d'intérêts; Conflits d'intérêts; Disclosure; Due process; Dérives arbitrales; Impartiality; Impartialité; Independence; Indépendance; Issue conflict; Justice arbitrale (administration); Principe de confiance; Procès équitable; Révélation; Transparence; Transparency

عقد الاعتماد الايجاري الدولي - عسالي, عبد الكريم (جامعة مولود معمري, 2015)
Keywords: Contrats; Convention UTAR de 1988; Crédit-bail international; Droit des testaments; اتفاقية اوتارا لسنة 1988; الاعتماد الايجاري الدولي; العقود; قانون الارادة

The Vienna Sales Convention and private international law - Wethmar-Lemmer, Marlene Muriel (University of Johannesburg, 2015)
The United Nations Convention on Contracts for the International Sale of Goods (the CISG or the Vienna Sales Convention) was adopted at a diplomatic conference of the United Nations held in Vienna during 1980. The Convention came into force on 1 January 1988. According to its preamble, the Convention is based on the premise that “the adoption of uniform rules which govern contracts for the international sale of goods and take into account the different social, economic and legal systems would contribute to the removal of legal barriers in international trade and promote the development of international trade”. The CISG has proven to be successful in its endeavour and currently has 74 member states representative of all legal traditions. As an international convention, the CISG has been lauded for its “simplicity, practicality and clarity”. Schlechtriem observed that the CISG has now gained worldwide acceptance. It has even been stated that the CISG has established a “world law on international sales” and that it has influenced several domestic sales laws. It is submitted that the CISG constitutes an important component of modern international commercial law or of the modern lex mercatoria. Therefore, a study that aims to establish a better understanding of the scope and functioning of the CISG and its relationship with domestic law, is of special relevance for the international business and legal community. The two basic methods of the unification of law, ie the unification of substantive law and the unification of private international law, have both been utilised in the field of the international sale of goods. The CISG is the most notable example of first mentioned method of unification.
Keywords: CISG; Choice of law clause; Conflict of laws; Contracts for the international sale of goods; Convention de Vienne; Export sales contracts; Lex mercatoria; Party autonomy; Sales; UNIDROIT Principles

Convergence of international trade and investment law in practice : how should investor-state arbitral tribunals engage with trade norms? - Chevry, Jonathan (European University Institute, 2015)
This thesis aims to provide an analytical framework to which investor-State arbitral tribunals can refer in cases where international trade law is invoked. The starting point of the present study is the trend in commentary on international trade and investment law, which makes the argument that international trade and investment law should be reconciled due to the clear "convergence" between (some of) their constitutive elements. This convergence argument is not misguided: there are similarities between the underlying principles of global trade and investment and, as such, a better coordination of these principles would be helpful for several reasons. Such reasons include legal certainty, reduction of transaction costs, better coherence in the operation of international agreements that now combine both trade and investment provisions, to name a few. However, no matter how reconcilable or converging the two disciplines may be, their enforcement mechanisms are structurally different and are likely to remain so even if the reforms towards a modernization of the investment dispute settlement (currently discussed at the EU policy level) are eventually implemented in the near future. In light of this last point, it is possible to claim that integration between trade law and investment law will only have limited or even negative effects if the trade and investment adjudicators continue to exercise their functions in an isolated manner, without taking cognizance of (i) the norms contained in the other discipline and (ii) the other adjudicator's scope of authority. Effective convergence of trade and investment entails a two-way process pursuant to which one adjudicator can use (i.e. take into account, refer to, apply, interpret and enforce) the law of the other and vice-versa. The thesis envisages one of the two dimensions of this process, namely the use of trade law by the investment adjudicator. Looking into the details of the convergence argument, the role of investment dispute settlement mechanism and the use of trade norms over the past two decades by litigants and arbitrators, the present study identifies both the legal techniques and obstacles these actors shall apply or go beyond in order to use trade norms in the most appropriate way and, more importantly, benefit from this use.
Keywords: Arbitrage; Arbitragem; Arbitration; Foreign investment; Foreign trade regulation; International commercial arbitration

Étude des règles d'indemnisation du préjudice dans l'arbitrage international : vers une indemnisation adéquate du préjudice - Mohamed Gamaleldin, Hossam (Université Paris 1, 2014)
Le recours à l'arbitrage par les opérateurs du commerce international a une finalité très importante, qui est celle de l'indemnisation appropriée et efficiente du préjudice. En vue d'évaluer celle-ci, notre étude adopte une recherche juridique détaillée en matière de réparation pour aboutir à un résultat satisfaisant concernant le principe le plus adapté en tant que cadre commun de l'opération d'évaluation de l'indemnisation du préjudice par les arbitres internationaux, en mettant notamment la lumière sur l'arbitrage CIRDI et CCI. À cette fin, il était nécessaire de suivre une analyse juridique tant sur les règles fondamentales que contingentes de l'indemnisation dans le souci d'avoir une perspective entière du processus de l'évaluation du quantum du préjudice. Un passage transversal était ainsi inéluctable sur les règles juridiques relatives à la réparation en droit privé français ainsi qu'en système juridique de Common Law. Au demeurant, un examen sur la codification de ces règles a été suivi dans le cadre des instruments internationaux de droit uniforme. Toutes ces réglementations ont inspiré le droit de l'arbitrage et ont servi comme des sources de celui-ci en matière de la réparation. Ces développements nous ont conduits à percevoir que l'indemnisation doit être adéquate en prenant en compte non seulement les préjudices subis, conformément au principe général de l'indemnisation intégrale, mais aussi tous les intérêts lésés. Sachant que certains préjudices ne sont pas mathématiquement évaluables, une indemnisation arbitraire s'impose dans ce cas. Un nouveau concept d' « indemnisation adéquate» du préjudice pourrait alors dans l'avenir s'imposer dans le droit de l'arbitrage international.
Keywords: Adequate compensation; Arbitrage international; Damages suffered; Dommages-intérêts; Full compensation; Indemnisation adéquate; Indemnisation intégrale; International arbitration; Intérêts lésés; Mercatoria; Prejudices; Process of the evaluation; Processus d'évaluation; Préjudices; Règles d'indemnisation; Réparation (droit international)

La contribution de la commission des Nations unies pour le droit commercial international (CNUDCI) à l'harmonisation et l'uniformisation du droit commercial international - Vieillard, Guillaume (Université de Bourgogne, 2014)
La Commission des Nations Unies pour le droit commercial international (CNUDCI), organe juridique principal de l’Organisation des Nations Unies à vocation universelle, a reçu de l’Assemblée générale de l’ONU pour mandat d’harmoniser, d’uniformiser et de coordonner le droit commercial international. Plus de quarante-cinq années après sa création, la CNUDCI poursuit son œuvre dans les domaines les plus importants du droit commercial international tels que l’arbitrage commercial international, la vente internationale de marchandises, le droit des sûretés, l’insolvabilité, les paiements internationaux, le transport international de marchandises, le commerce électronique, la passation de marchés et le développement des infrastructures. En adoptant divers instruments juridiques par le biais d’un processus de négociation intégrant les Etats ainsi que certaines organisations intergouvernementales et non gouvernementales, la CNUDCI met à la disposition de la communauté internationale des marchands les outils juridiques nécessaires permettant de faciliter et de sécuriser les opérations du commerce mondial. La présente thèse analyse la manière dont la CNUDCI contribue au renforcement du droit commercial international en adoptant un ensemble de règles juridiques sur les opérations commerciales internationales.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitration; CNUDCI; Commerce international; Compétence normative; Coordination; Droit commercial (droit international); Droit commercial international; Harmonisation; Harmonization; International trade law; Modernization; Nations unies. Commission pour le droit commercial international; Normative action; UNCITRAL; Unification internationale; Uniformisation

O diálogo sustentável entre o direito do comércio internacional e o direito à água - Vieira, Andréia Costa (Universidade de São Paulo, 2014)
O Direito Internacional Contemporâneo é um sistema pluralista e tem se defrontado com temas os mais diversos na atual agenda internacional. Um dos temas que têm merecido a preocupação do Direito Internacional é a chamada crise da água, assim entendida como a escassez, a poluição, a crise de abastecimento, a sede do setor privado para entrar nesse mercado e os diversos conflitos internacionais em torno da água. A problemática da água envolve, principalmente, três áreas distintas do Direito Internacional, a saber: o Direito do Comércio Internacional, o Direito Internacional do Meio Ambiente e o Direito Internacional dos Direitos Humanos. Para lidar com essa problemática e trazer soluções concretas à questão da água, a presente pesquisa sugere um diálogo entre essas distintas áreas do Direito. Parte do pressuposto do Direito Internacional como um sistema, apesar dos seus distintos regimes, identificando-o frente ao fenômeno da globalização e seu consequente fenômeno da governança global, emoldurado por distintos atores internacionais, distintas normas de direito e distintos fóruns de aplicação. Apresenta o Regime do Comércio Internacional e o Regime do Meio Ambiente Internacional, nos quais já se inserem as questões hídricas, e identifica possíveis diálogos entre esses regimes, moldados pela noção de desenvolvimento sustentável. Afirma a existência do Regime Internacional da Água Doce e suas duas bases de construção estrutural e desenvolvimento: o Direito Internacional da Água Doce para fins diversos da navegação e o Direito Humano à Água. Apresenta os elementos de cada uma dessas defesas e conclui pela existência e desenvolvimento desse regime, cuja consolidação deve ser feita através de um diálogo com o Regime do Comércio Internacional. Nesse proposto diálogo, apresenta dois tipos de interação entre regimes: a interação conflitual e a interação relacional. Como interação conflitual, faz dialogar as normas do GATT e do GATS com as normas do Regime Internacional da Água Doce. Como interação relacional, traz propostas concretas que harmonizam o comércio internacional e a proteção das águas doces, a saber: a criação de uma agência especializada, no âmbito da ONU, para assuntos hídricos; a criação de uma Convenção Quadro sobre recursos hídricos e a criação de um Mecanismo de Desenvolvimento Limpo para a água e seu consequente mercado de water certificates. Após detalhar esse hibridismo das normas sobre recursos hídricos, conclui pela legitimidade dessa interação relacional e pelos ganhos que podem advir em favor de um desenvolvimento sustentável, através desse diálogo entre o Direito do Comércio Internacional e o Direito à Água. The contemporary International Law is a pluralistic system that has faced distinct issues in the contemporary international agenda. One of these issues is the so termed water crisis, which comprises scarcity, pollution, water supply matters, the eagerness of the private sector to dominate it and the different international water conflicts. Water issues have mainly evolved through three different subjects of International Law: International Trade Law, International Environmental Law and International Law of Human Rights. To deal with these issues and to bring about real solutions to the water crisis, this research suggests a dialogue between these three different law subjects. It starts with the conjecture that International Law is a system, despite its different regimes, and identifies it within the phenomenon of globalization and its consequent phenomenon of global governance - shaped by distinct international actors, distinct rules and distinct adjudication fora. It presents the International Trade Regime and the International Environmental Regime, within which the water issues can be found, and points out possible dialogues between these regimes, shaped by the notion of sustainable development. It affirms the existence of the International Freshwater Regime and its two structural and developmental bases: the International Law of Non-Navigational Uses of Watercourses and the Human Right to Water. It introduces each element of these two subsystems and it concludes for the existence and development of the International Freshwater Regime, whose consolidation should be built on a dialogue with the International Trade Regime. Within such a proposal of dialogue, it presents two kinds of regime interaction: a conflict interaction and a relational interaction. As a conflict interaction, it brings about a dialogue between the GATT and the GATS rules and the International Freshwater Regime rules. As a relational interaction, it points out real instruments to harmonize international trade law and freshwater protection: the creation of a specialized agency under the United Nations auspices; the creation of an umbrella-convention on water resources; and the creation of a clean development mechanism and its consequent water certificates market. After explaining the hybridism of the water resources rules, it concludes for the legitimacy of this relational interaction and the gains it may have towards a sustainable development through a dialogue between International Trade Law and the Right to Water.
Keywords: Abastecimento de água; Commerce international; Comércio internacional; Dialogue of sources; Direito comercial internacional; Direito das águas; International law regimes; Recursos hídricos; Right to water; Trade of water; Água doce

International sales contracts in Congolese law : a comparative analysis - Kahindo, Nguru Aristide (University of South Africa, 2014)
To regulate and facilitate are the main functions of legal rules. These purposes are achieved by a harmonised legal system by which the law becomes identical in numerous jurisdictions. The process to unify the law of sale internationally started in the 1920s and culminated, in 1988, in the implementation of the CISG. This Convention intends to provide clarity for most international sales transactions by regulating the formation of contracts, and the rights and obligations of the seller and the buyer resulting from the contract. The CISG has these days enjoyed much ratification and influenced a number of legislation reforms worldwide. Despite the role it played during the drafting process of the CISG, the DRC has not yet ratified it. Instead, the country continued to rely, until recently, on colonial legislations which had become out-dated, and inadequate to meet modern international sales contracts requirements. The situation appears to have been improved a year ago as the effect of the adoption of OHADA law whose Commercial Act is largely inspired by the CISG. Because the introduction of OHADA law in the DRC is very recent, this study intends to assess the current state of Congolese sales law by comparing it with the CISG and South African law, which is non-CISG but modernised. The comparative study aims at establishing whether current Congolese law, as amended by OHADA law, is sufficient or has shortcomings; if it has some, it aims to identify those shortcomings, and make suggestions for their improvements. After discussion, it has been discovered that the ratification of OHADA law has significantly improved Congolese domestic sales law. Given that there remain certain unresolved shortcomings in Congolese international sales law, however, the study ends by a proposal for the accession of the DRC to the CISG in order to fill them.
Keywords: Congo (Democratic Republic); Congolese contract law; Congolese sales law; Contracts; Export sales contracts; Formation of the contract; International sales law; OHADA law; Obligations of the buyer; Obligations of the seller; Sale of goods; South Africa; South African contract law; South African sales law

Regulating trade in petroleum under the WTO Regime: trade rules vs. reality of the petroleum industry - Bitenov, Gani (McGill University, 2014)
This thesis critically assesses the effectiveness of WTO legal rules in the regulation of international trade in petroleum and highlights potential conflicts between competing resources of energy from the WTO regime’s perspective. The theoretical framework of the thesis is built on the concepts used in natural resource economics, trade theories and international relations. On the basis of Hotelling’s rule of natural resource economics, it proposes a model that reconciles the use of petroleum and the development of renewable sources of energy in the power generation sector, which prospectively can be adopted with respect to the transport sector and other sectors involving energy use. The proposed model may improve global sustainable development. However, it is argued that WTO rules are not properly designed to regulate trade in petroleum and, if applied without due respect to specific issues pertaining to the petroleum industry, would obstruct the achievement of the social optimum, and detrimentally affect the national economies of WTO members and global welfare in general. To improve the WTO system, I propose a reformation of its normative ideology through the introduction of the strategic trade policy theory in complement to the neoclassical theory of trade, at least when trade in energy is concerned. On the basis of the study of the applicability of WTO rules to trade in petroleum and a review of proposals put forward by other scholars to improve the regulation of trade in energy, it is argued that the most effective way to improve the trading regime is to negotiate a new general agreement on trade in energy.The role of the WTO in the regulation of trade in energy is analyzed through a regime management theory borrowed from international relations studies. It is argued that the WTO as a regime manager is capable of improving the regime by properly maintaining the existing equilibrium and by initiating, and leading in negotiations of a new equilibrium.
Keywords: Petroleum industry and trade; Trade regulation; WTO trade rules

Verkäufer und Käufer im Spiegel regionalen und universalen Einheitsrechts - Tchameni, Joseph-Augustin (Universität Wien, 2014)
Die Koexistenz des „regionalen" und „universalen“ Einheitsrechts wirft eine Reihe von Rechtsfragen auf, deren Behandlung und Lösung auf den Gebieten des Privat- und Wirtschaftsrechts nicht nur Schwierigkeiten bereiten, sondern auch erhebliche Umstellung erfordern. Einerseits bietet der wachsende Bestand regional vereinheitlichter oder harmonisierter Rechtsnormen gegenüber dem disziplinären Rechtswesen des Völkerrechts ein anderes, facettenreiches Bild und bringt damit neue Forschungsweisen sowie ein anderes Denken und Wissen im Bereich des Privat- und Handelsrechts hervor. In der Erforschung der Spannungsverhältnisse und Lösungsansätze, die sich aus Wechselwirkungen, Konkurrenzverhältnissen sowie Konfliktlagen zwischen derartigen Rechtswesen ergeben, stehen die Rechtswissenschaften noch am Anfang. Andererseits führt die Entwicklung der elektronisch unterstützten Gestaltung sämtlicher wirtschaftlicher Transaktionen (E-Commerce) einen Wandel in der Wirtschaft herbei. Der Kauf von Waren bei einem Online-Versandhaus, die elektronische Kommunikation zwischen einer Handelskette und ihren Zulieferbetrieben, Teleshopping, die elektronische Unterstützung von Warentransporten stellen Beispiele für diesen Wandel dar. Der Internetzugang erleichtert die Intensivierung des An- und Verkaufs von Waren über staatliche Grenze hinweg. Bei derartiger „Grenzenlosigkeit“ wirtschaftlicher Nutzung und aufgrund der fortschreitenden Globalisierung stellt sich im Zuge des Geschäftsverkehrs zwischen Unternehmern (Kaufleuten) oder zwischen Unternehmer und Verbraucher als Parteien aus rechtlicher Sicht neben den unverzichtbaren vertraglich zu regelnden Punkten auch die Frage nach dem auf den Kaufvertrag anwendbaren Recht. Aus dieser Perspektive analysiert die Arbeit umfassend und kritisch gegenüber , - nach einer systematischen Darstellung des UN-Kaufrechts und der(s) OHADA (Rechts insb AU.DCG) hinsichtlich der Entstehung, des Aufbaus, der Grundzüge, der Bedeutung unter Berücksichtigung des Verhältnisses zwischen den beiden Regelwerken und deren Eigenschaften -, den Kaufvertrag zwischen dem Verkäufer und dem Käufer ins System des Handelskaufs der OHADA im Vergleich zu CISG-Regelungen.
Keywords: AUDCG; Acheteur; OHADA; Seller and buyer in the mirror of regional; Uniform law; Universal uniform law; Universalen Einheitsrechts; Vendeur; Verkäufer und Käufer im Spiegel regionalen

L'interprétation par l'organe d'appel de l'OMC à l'aune de l'objectif de sécurité juridique - Legendre Le Cloarec, Mathilde (Université Paris 1, 2013)
L’interprétation des dispositions des accords de l’OMC constitue l’enjeu principal de la phase d’appel du système de règlement des différends. Ce processus intellectuel vise à établir le sens des normes. La compétence d’interprétation procure donc un pouvoir normatif important que l’Organe d’appel est, en pratique, le seul à détenir en dernier ressort à l’OMC. Cependant, elle est encadrée par l’obligation, imposée par le Mémorandum d’accord sur les règles et procédures régissant le règlement des différends, d’assurer la sécurité et la prévisibilité du système commercial multilatéral. Or, l’interprétation est une opération, par nature, quasi discrétionnaire. Elle ne peut donc théoriquement pas répondre à l’objectif de sécurité. Cette thèse montre que l’Organe d’appel parvient pourtant à faire face à ce double défi : procurer, par le biais de l’interprétation, un sentiment de sécurité juridique aux membres, et assurer un minimum de sécurité juridique au système. L’Organe d’appel a conscience que l’interprétation est avant tout perçue comme une opération technique et soigne sa mise en œuvre. Sa technique interprétative rationnelle, sans être en mesure de garantir la prévisibilité, lui permet néanmoins de procurer aux membres de l’OMC un sentiment de sécurité juridique. Sa politique interprétative, basée sur l’intégration du droit de l’OMC dans le système juridique international et sur le développement et le maintien de l’unité du système OMC, lui permet, quant à elle, d’instaurer de facto une situation de relative sécurité juridique. L’Organe d’appel parvient ainsi à faire de la sécurité juridique un principe d’interprétation.
Keywords: Appellate body; Dispute settlement system; Interprétation; Organe d'appel; Organisation mondiale du commerce; Organisation mondiale du commerce. Organe d'appel; Réglement des différends; Sécurité juridique; WTO

Les conventions ACP-EU et les sanctions économiques de l'Union européenne contre les Etats ACP : le cas du Togo - Nikabou, Lantame Jean (Université de Strasbourg, 2013)
L’Accord de Cotonou, signé en juin 2000 entre l’Union européenne et les États d’Afrique, des Caraïbes et du Pacifique (ACP), se caractérise par un respect des droits de l’homme, des normes démocratiques et de l’État de droit d’une part, et la quête d’une conformité des normes aux principes de l’Organisation mondiale du commerce (OMC), d’autre part. En effet, la politique de développement mise en place par l’Europe au profit des États ACP a vu le jour avec le Traité de Rome et la création du Fonds européen de développement au profit des ces pays. Pendant longtemps, le partenariat, essentiellement économique, a octroyé d’énormes avantages aux pays ACP en vue d’assurer leur développement. Depuis bientôt deux décennies que les normes politiques ont été insérées dans ce partenariat, force est de constater que quelques pays, dont le Togo, demeurent toujours réticents quant à l’instauration de réelles réformes démocratiques en vue d’assurer une véritable alternance politique. En dépit des sanctions infligées çà et là par l’Union européenne, ces pays trouvent un appui auprès de la Chine qui mène, avec les pays d’Afrique, un partenariat en toute exclusion de la société civile.
Keywords: ACP; Accord ACP-UE de Cotonou; Accord de Cotonou; Afrique; Chine; Cotonou agreement; Economic partnership between EU and ACP; Partenariat; Partenariat économique; Partnership between China and Africa; Pays ACP; Pays de l'Union européenne; Relations extérieures; Relations économiques internationales; Togo; Traités; UE

Les acteurs privés dans le système de règlement des différends de l’Organisation Mondiale du Commerce (OMC) - Barafi, Jamal (Université de Strasbourg, 2013)
Le règlement des différends forme la clef de voûte du système commercial multilatéral et une contribution sans précédent de l'OMC à la stabilité de l'économie mondiale. Sans un moyen de régler les différends, le système fondé sur des règles ne serait d’aucune utilité car celles-ci ne pourraient pas être appliquées. Cette organisation est dotée de moyens institutionnels et de régulation propres. L’ORD, Organe de règlement des différends, arbitre des différends commerciaux internationaux qui vise à garantir le bon fonctionnement de l’OMC et à la correction des défauts majeurs apparus lors du GATT. Il est aujourd’hui l’un des mécanismes interétatiques parmi les plus actifs sur le plan international.Pourtant, le jeu économique international n’implique pas seulement les États, les acteurs privés, affectés par les actes et les comportements commerciaux, y cherchent à jouer un rôle concret et efficace. Cette étude aborde la question de la possibilité d’intervention des acteurs privés aux procédures de règlement des différends de l’OMC. Elle a pour objet de présenter les formes actuelles d’intervention de ces acteurs au sein de ces procédures et les possibilités d’un renforcement de leur participation au sein de l’OMC.
Keywords: Acteur privé; Acteurs non étatiques; Amici curiae; Amicus curiae; Groupe spécial; Intervention; ONG; Organe d'appel; Organe de rêglement des différends; Organisation mondiale du commerce (Organe de règlement des conflits); Private actors; Procédure commerciale; Secteur privé; Voies de recours

The harmonisation of rules on the recognition and enforcement of foreign judgments in the Southern African Customs Union - Rossouw, Mandi (University of the Western Cape, 2013)
The thesis considers the approaches followed by the European Union with the Brussels Regime, the federal system of the United States of America under the ‘full faith and credit clause’; the inter-state recognition scheme under the Australia and New Zealand Trans- Tasman judicial system; as well as the convention-approach of the Latin American States. It finds that the most suitable approach for the SACU is the negotiation and adoption by all SACU Member States of a multilateral convention on the recognition and enforcement of foreign judgments, comparable to the 1971 Convention of the Hague Conference on Private International Law; the EU Brussels I Regulation and the Latin-American Montevideo Convention, as complemented by the La Paz Convention. It is imperative that a proposed convention should not merely duplicate previous efforts, but should be drafted in the light of the legal, political and socio-economic characteristics of the SACU Member States. The current legislative provisions in force in SACU Member States are compared and analysed, and the comparison and analysis form the basis of a proposal for a future instrument on recognition and enforcement of foreign judgments for the region. A recommended draft text for a proposed Convention on the Recognition and Enforcement of Foreign Judgments for the SACU is included. This draft text could form the basis for future negotiations by SACU Member States
Keywords: Civil and commercial transactions; Cross-border litigation; Foreign judgments; International Trade; Recognition and enforcement; Regional integration; Trade facilitation

La fonction de représentation extérieure commune des organisations d’intégration ouest africaines dans les négociations commerciales - Yougbaré, Robert (Université de Ouaga 2, 2012)
Le régionalisme est un phénomène qui a pris de l'ampleur dans le monde, en général, et sur le continent africain en particulier. L'Afrique découvre le phénomène en même temps qu'elle expérimente l'étatisme, la forme d'organisation sociopolitique sous laquelle le continent s'est émancipé de ses anciens colonisateurs. Des indépendances à nos jours, en dépit de sa constance, le phénomène a connu une redynamisation, qui l'a conduit à une certaine unité théorique. Face à la constance du phénomène, l'on est en droit de s'interroger sur sa logique (MATTI, 1999), sur sa raison d'être. En partant d'une approche sociologique des relations internationales, aucun phénomène, aucune organisation spécifique n'est le fruit d'un hasard : chaque institution répond à un besoin donné. C'est de cette hypothèse qu'est parti le présent projet de recherche, qui s'est assigné pour objectif d'expliquer la rationalité du régionalisme, en général, et de sa dimension extérieure, c'est-à-dire, l'unité de front face au monde qu'elle constitue, en particulier. Le besoin d'un front d'action collective dans les relations internationales est évident pour les Etats africains, en proie à une marginalisation croissante dans les relations internationales. L'Etat africain manque, à lui seul, des facteurs, notamment le facteur structurel, qui pourraient inverser la tendance. Il lui faut par conséquent, d'autres approches. Le régionalisme est l'une de celles-là. L'étude s'est focalisée sur le sous-continent ouest africain, pour les besoins de vérification empirique. Elle s'est également inscrite dans le cadre des relations commerciales internationales pour y analyser le potentiel d'action internationale des organisations d'intégration africaines. Dans ce cadre, au-delà de l'explication de la ratio legis de la fonction de représentation extérieure commune -la fonction qui consiste pour une organisation à unifier et / ou coordonner l'action extérieure de ses membres, l'étude a porté sur l'existence théorique des conditions juridiques d'exercice de la fonction par deux des principales organisations d'intégration de la sous-région que sont la Communauté Economique des Etats de l'Afrique de l'Ouest (CEDEAO) et l'Union Economique et Monétaire Ouest africaine (UEMOA). Il s'est révélé qu'en dépit de quelques incertitudes résiduelles que la pratique peut aisément lever, ces organisations s'inscrivent bien dans cette logique de servir d'interface à leurs membres pour une action collective efficace dans les relations commerciales internationales. Bien au-delà de l'investigation théorique, l'étude a scruté le terrain empirique, pour se rendre compte de l'exercice éventuel de la fonction dans la pratique des organisations ouest africaines. Elle a examiné les conditions de leur présence dans le système juridique commercial multilatéral (le système de l'OMC) et leur implication dans un dossier qui semblait constituer une porte d'entrée dans l'arène de la diplomatie commerciale multilatérale, en l'occurrence, le dossier du coton africain à l'OMC. Leur implication y a été, malheureusement, en deçà de leur possibilité d'action. Toujours est-il que, d'un point de vue empirique, l'étude a examiné la participation des deux organisations dans la négociation de l'Accord de partenariat économique (APE) Afrique de l'Ouest - Union européenne. Dans ce dossier, les organisations ouest africaines ont fait preuve d'un certain leadership, affichant ainsi leur détermination à assumer cette fonction de représentant de la région. Certes, les résultats sont encore incertains, mais un certain satisfecit se dégage dans le camp ouest africain, pour avoir résisté face à l'avalanche des négociateurs européens. Le seul point critique demeure dorénavant l'aménagement de la participation des Etats dans le mécanisme de représentation commune, de façon à ce que chacun y voit individuellement un instrument de sa politique extérieure, pour une durabilité du dispositif. Un affinement dans ce sens renforcera et rendra réelle, la fonction de représentation extérieure commune dans les mains des organisations ouest africaines. Regionalism is a growing phenomenon in the world in general, and particularly on the African continent. Africa experimented at the same time regionalism and the modern state. From independence to the present days, despite its constancy, the phenomenon has been reinvigorated, leading to a degree of theoretical unity. Faced with the constancy of the phenomenon, we are entitled to question its logic (MATTI, 1999), its raison d'être. From a sociological approach to international relations, no phenomenon or specific organisation arises by chance: each institution responds to a given social need. This is the starting point for the present research project, which has set itself the objective of explaining the rationality of regionalism in general, and of its external dimension, that to say, the blocs it constitutes regarding the rest of the world, in particular. The need for a collective action in international relations is obvious for African states, which are increasingly marginalised in international relations. The African state, left alone, lacks the factors, particularly the structural factor, that could reverse the trend. It therefore needs other approaches. Regionalism appears to be one of them. The study focused on the West African sub-region, for the purposes of empirical verification. It also looked at international trade relations in order to analyse the potential for international action of African integration organisations. In this context, in addition to explaining the ratio legis of the function of common external representation - the function that consists of an organisation unifying and/or coordinating the external action of its members - the study focused on the positivity of legal conditions for the exercise of this function by two of the main integration organisations in the sub-region, namely the Economic Community of West African States (ECOWAS) and the West African Economic and Monetary Union (WAEMU) It turned out that, despite a few residual uncertainties that can easily be resolved in practice, these organisations are very much in line with this logic of serving as an interface for their members to ensure effective collective action in international trade relations. In addition to theoretical research, the study also looked at empirical evidence of how West African organisations perform this function in practice. It examined the conditions of their presence in the multilateral trade legal system (the WTO system) and their involvement in an issue that seemed to constitute a gateway into the arena of multilateral trade diplomacy, in this case the African cotton issue at the WTO. Unfortunately, their involvement fell short of their potential. Still from an empirical point of view, the study examined the participation of the two organisations in the negotiation of the West Africa-European Union Economic Partnership Agreement (EPA). The West African organisations have shown a degree of leadership in these negotiations, demonstrating their determination to represent the region. Admittedly, the results are still uncertain, but there is a certain satisfaction in the West African camp for having withstood the avalanche of European negotiators. The only critical point from now on is the way in which the States participate in the common representation mechanism, so that each one sees it individually as an instrument of its foreign policy, to ensure the sustainability of the mechanism. Refining the mechanism in this way will strengthen and make real the function of common external representation in the hands of West African organisations.
Keywords: Afrique de l'Ouest; CEDEAO; Common trade policy; ECOWAS; External common representation; Intégration régionale; Négociations commerciales; Politiques commerciales communes; Regional integration; Représentation extérieure commune; Trade negociations; UEMOA; WAEMU; West Africa

Les normes privées relatives à la qualité des produits : étude d’un phénomène juridique transnational - Sarrouf, Muriel (Université Paris 2, 2012)
Les normes privées intéressent le droit international à un double titre : se développant en marge du système interétatique classique, elles constituent l’un des visages d’une régulation privée transnationale émergente et soulèvent la question théorique de leur statut en droit international. Par ailleurs, leurs effets sur le commerce international (et particulièrement le fait qu’elles constituent un obstacle aux exportations des PED vers les marchés occidentaux), conduisent à s’interroger sur l’opportunité et les modalités de leur réglementation par le droit international des échanges. En dépit de leur diversité empirique qui rend difficile toute tentative de systématisation et de qualification juridique, nous considérons que la qualité des produits, qui constitue le fondement téléologique commun des normes privées, permet d’en justifier l’unité théorique et de les considérer comme un phénomène juridique à part entière. Nous démontrerons que les normes privées sont l’une des manifestations d’un droit transnational se développant en parallèle du droit interétatique « classique » et qu’elles jouissent par conséquent d’un statut juridique propre. De ce fait, leurs rapports avec la branche du droit international qu’elles intéressent le plus directement, le droit international des échanges, ne peuvent se limiter à l’approche classique de réglementation (ou approche « répressive », en ce qu’elle a pour seul but d’en limiter les effets restrictifs pour le commerce) mais doivent se concevoir dans une optique de coordination. The recent proliferation of private standards is not only of growing interest to economists who seek to evaluate its impact on trade flows; it is also relevant to international law, particularly to international economic law, in a double perspective. First, from the perspective of legal theory, the legal status of private standards has still to be determined. Second, from an empirical standpoint, private standards have the potential to negatively impact the access of developing countries to the markets of developed countries. This raises the question of the opportunity and modalities of submitting them to the disciplines of the WTO Agreements. This study demonstrates that private standards are one of the expressions of broader ‘transnational law’, a body of law that has been developing in parallel to ‘traditional’ state-centered international law. This implies that international law cannot merely consider private standards as an object to be disciplined; rather, the traditional ‘repressive’ approach should be rejected in favor of a more collaborative approach stressing the interrelations between the two bodies of norms as well as possible forms of coordination.
Keywords: Droit commercial (droit international); Droit transnational; Legal pluralism; Normes privées; OMC; Pluralisme juridique; Private standards; Qualité des produits; Transnational law; WTO

Le droit alimentaire européen dans les échanges commerciaux entre l'Union européenne et les pays subsahariens - Nyama, Annie Laurence (Université Montpellier 1, 2012)
Les échanges commerciaux de denrées alimentaires entre l'Union européenne et les Etats Subsahariens sont en constante augmentation et sont encadrés par les grands principes du droit alimentaire européen, composante du droit de la consommation. Ces grands principes énoncent des règles d'information des consommateurs, de sécurité, de conformité et de traçabilité des produits alimentaires qui doivent être respectés par toutes les parties prenantes du secteur agroalimentaire et des ses filières. C'est donc une masse importante de règles internationales, communautaires européennes qui se combinent aux textes nationaux. Les exportateurs / importateurs au sein de la Communauté, et les professionnels des pays tiers, mettent en œuvre ces règles dans les contrats de vente internationales des denrées. Les problèmes de santé et de sécurité sont posés par les consommateurs inquiets de leur protection. Mais les producteurs seront attentifs à l'évolution des règles qui protègent les consommateurs car elles conditionnent les activités de production, de transformation de transport, de stockage et de commercialisation. Certes, l'Afrique subsaharienne occupe une place faible dans le commerce mondial, mais son importance dans les échanges avec le continent européen, reste un facteur d'encouragement de la production des produits africains commercialisables. A cet effet, les pays subsahariens ne peuvent plus se contenter d'une réglementation locale, inadaptée, bien lacunaire et peu effective, au regard de l'importance des solutions aux questions sanitaires alimentaires dans le cadre du commerce mondial. D'ailleurs les importateurs européens imposent, contractuellement, à leurs partenaires africains le respect des impératifs sanitaires européens sans lesquels ils ne pourraient mettre les aliments importés en circulation en Europe. La thèse met en évidence un impératif de modernisation des instruments juridiques et institutionnels en Afrique subsaharienne. La place que prennent désormais les normes, quelles qu'en soient les différentes variantes est, à cet égard, très instructive. Les normes permettent aux producteurs et exportateurs des pays en développement de raccourcir les opérations complexes de compréhension des textes impératifs et des principes techniques et managériaux très modernes.
Keywords: Commerce international; Consumer law; Droit alimentaire européen; Droit de la consommation; Echanges Nord-Sud; European food law; International Trade; North-South trade; Sanitary food safety; Sécurité sanitaire alimentaire

Les intégrations économiques régionales à l'ère de l'OMC : l'évolution de l'article XXIV - Bhouri, Houda (Université Laval, 2012)
L'article XXIV constitue le fondement et le cadre juridique des accords commerciaux régionaux (ACR) sur la base duquel sont examinés les accords notifiés à l'Organisation Mondiale du Commerce (OMC). Cet article est comme une exception au principe de la nation la plus favorisée, clé de voûte du système commercial multilatéral. L'article XXIV s'est au cours du temps, avéré être une disposition ambiguë et fluctuante. Ses imprécisions ont donné lieu à des interprétations divergentes. Ceci a engendré des controverses entre les Membres de l'OMC qui, malgré les efforts, n'ont pas réussi à résoudre ses lacunes. L'ambiguïté des critères de l'article XXIV a été exploitée par les États donnant lieu à une pléthore d'ACR dont la portée et le contenu sont loin d'être conformes à l'Article XXIV. Cette situation a créé une brèche dans les principes fondamentaux du système commercial multilatéral à cause de la discrimination que ces systèmes préférentiels engendrent au détriment des tierces parties. La première partie de cette thèse décrit la genèse de l'article XXIV et les objectifs que les fondateurs de l'accord Général sur les tarifs douaniers et le commerce (GATT) attendaient de la création d'intégrations économique plus poussées. Ces derniers n'ont pas prévu les abus dans son application, qui ont été tels qu'ils pouvaient mettre en péril l'intégrité du système commercial multilatéral. Cet état de fait déclencha une alarme appelant à une remise en question de tout le système. Malgré les efforts, l'article XXIV ne semble pas encore refléter une évolution décisive dans son application. De nombreux défauts intrinsèques et extrinsèques du système commercial multilatéral sont considérés dans la deuxième partie de la thèse, expliquant l'échec des tentatives d'amélioration. Il est clair qu'une évolution ne pourrait être notable que si elle était « endogène », exprimant une volonté commune des Membres. Ainsi, nous faisons des suggestions d'ordre autant formel que matériel, pouvant permettre à notre avis, d'apporter une contribution à l'amélioration de cette situation conflictuelle. Il reste néanmoins clair que la nature complexe et « dynamique » du problème rend toute évolution incertaine. Il faut rester vigilant afin que la situation évolue vers la réalisation de plus d'ouverture mais ne retourne pas vers une remise en cause du multilatéralisme.
Keywords: GATT; OMC; Organisation mondiale du commerce; Régionalisation économique; Tarifs douaniers; WTO

A legal analysis of the application of articles I and III of the GATT 1994 on the economic development of ECOWAS member states - Ogbonna, Joseph Ifeanyichukwu (Brunel University, 2012)
This dissertation examines the tension inherent in the relationship between the Economic Community of West African States (ECOWAS) as Member States Parties of the GATT/WTO and the GATT/WTO regime. It focuses specifically on the tension triggered off by the requirements of Article I – the Most-Favoured-Nation principle (MFN) and Article III – the National Treatment principle (NT) GATT 1994. It shows that while the non-discrimination principles are meant to promote trade liberalisation and economic growth, they produce the opposite effect in developing and least developed countries like ECOWAS and aggravate the tension between those countries and the WTO. It argues that the MFN is used to deny market access to the developing countries by exposing them to stiff but unequal competitive conditions and the NT to deny national governments the policy space to protect and promote national industries, employment and economic growth. It challenges the general assumption that the MFN and the NT are good and in the interest of all the WTO Members and rather identifies them as lynch-pins of economic development in the ECOWAS region. It also shows, contrary to the assumption of non-participation, how the ECOWAS High Contracting Parties are adapting their trading systems and harmonising their laws to the key provisions of Articles I and III of the GATT. It shows that the principles of non-discrimination are the outcome of the standard-setting procedures legally formulated as the SPS and TBT Agreements which favour the developed countries and how the Dispute Settlement Body has rejected the ‘aims-and-effect’ approach, taken a literal approach, overly emphasising trade liberalisation to the neglect of market access and economic development. This dissertation concludes that it is pre-mature for ECOWAS to assume Articles I and III obligations and recommends using the provisions of Article XXIV to build up effective influence through regional organisations and incrementally uniting to transform the GATT.This study is funded by the Brunel Law School
Keywords: ECOWAS; GATT; Tension; WTO; World Trade Organisation

Le respect de la propriété intellectuelle d'autrui dans la vente internationale de marchandises : une approche de la Convention de Vienne coordonnée avec le droit de la propriété intellectuelle - Verville, Sophie (Université Laval, 2012)
Le respect de la propriété intellectuelle d'autrui dans la vente internationale de marchandises ; Une approche de la Convention de Vienne coordonnée avec le droit de la propriété intellectuelle L'article 42 de la Convention de Vienne impose au vendeur de livrer la marchandise libre de tout droit ou prétention de tiers fondé sur la propriété intellectuelle. L'obligation s'inscrit dans une logique de protection des facultés de revente et d'utilisation sur les territoires envisagés. Ses conditions d'entrée enjeu requièrent cependant l'analyse de ce que chaque contractant connaissait ou ne pouvait ignorer au sujet de la propriété intellectuelle du tiers. Ce passage de la Convention connaît des interprétations variées. Le courant jurisprudentiel dominant tend à retenir l'imputabilité systématique de l'acheteur professionnel tandis que le courant doctrinal dominant impose une rigueur beaucoup plus stricte au vendeur. Afin de contribuer à une interprétation plus uniforme et prévisible de l'article 42, le projet s'attache à le replacer sur la trame plus générale du commerce international, où le droit de la propriété intellectuelle pose des obstacles aux mouvements transfrontaliers des marchandises. L'article 42 est d'abord comparé avec la théorie de l'épuisement des droits, qui prévoit la fin d'une emprise du droit intellectuel sur les supports de création. Le mécanisme de l'article 42 est ensuite mis en parallèle avec les moyens qui sont accessibles aux parties à la vente pour prévenir le problème d'interférence avec les droits intellectuels. À la lumière des modes limités de publicité des droits intellectuels et de la complexité des régimes conçus pour protéger les créations, il appert que ce domaine ne permet pas de prévenir efficacement les risques pouvant contrecarrer la vente. La solution proposée par la Convention de Vienne est enfin confrontée aux principes généraux dont elle s'inspire. Ceux-ci disposent de présomptions d'égalité et de compétence à l'égard des opérateurs, lesquelles ne peuvent être repoussées que par une démonstration de déséquilibre substantiel. Le cas échéant, l'équilibre peut être rétabli par l'intensification des obligations d'information et de coopération sur les épaules du contractant qualifié au bénéfice du plus faible. Il ressort de la démarche que l'équilibre contractuel qui sous-tend l'article 42 se fonde sur une répartition particulière de la prévention. La spécificité des droits intellectuels le requiert. Le respect de ces droits dans la vente internationale revient donc généralement aux deux contractants.
Keywords: Distribution (Économie politique); Intellectual property; Propriedade intelectual; Propriété intellectuelle; Vente internationale

Le régime juridique du commerce des produits agricoles dans le droit de l'OMC - Zouré, Théophane Noël (Université de Genève, 2011)
La multifonctionnalité de l'agriculture est un sujet fondamental dans les négociattions du Cycle de Doha. Reconnaître cette multifonctionnalité de l'agriculture revient à lui assigner des fonctions non commerciales. Cette thèse se penche sur le droit de l'OMC pour voir s'il prend en compte le particularisme de l'agriculture. La première partie est consacrée au GATT de 1947. Elle montre que le GATT ne distinguait pas les produits agricoles des produits industriels. La seconde partie est consacrée à l'Accord sur l'agriculture de 1995 qui reconnaît à l'agriculture des fonctions non marchandes. Cette reconnaissance n'a pas de portée juridique réelle. La troisième partie est consacrée au Cycle de Doha. L'enjeu de ce Cycle réside dans la traduction de la multifonctionnalité en normes juridiques. Nonobstant les diverses propositions, l'issue de ces négocations est incertaine. Faute de réserver à la multifonctionnalité un traitement adéquat, l'OMC sera fragilisée et on assistera à une montée du bilatéralisme.

Uluslararası Ticaret Hukukunda vesaik mukabili ödeme - Atalay, Ersan (Yeditepe Üniversitesi, 2011)
Uluslararası ticaretle ilgili alım satım sözleşmelerinde temel olan edimlerden birisi de ödeme dir. Türk hukuk sisteminde kullanıldığı şekli ile Vesaik mukabili ödeme uluslararası ticaretin önemli ödeme araçlarından birisidir.Uluslararası ticaret hukukunda bu konu hakkında tüm ülkeler açısından geçerli olan bir yasal düzenleme yoktur. Bu yüzden bazı örgütler, bu boşluğu doldurmayı amaçlamışlardır. Bu örgütlerden biri Uluslararası Ticaret Odası dır. Uluslararası Ticaret Odası, uluslar arası ticaretin yeknesak kurallara bağlanmasını amaç edinmiştir. Bunun için bazı broşürler yayınlamaktadır. Vesaik Mukabili Ödeme' ye ilişkin olarak, URC 522 kısaltmasıyla anılan, Tahsiller İçin Yeknesak Kurallar broşürünü yayınlamıştır. En son gözden geçirme çalışmaları 1995 yılında yapılmıştır. Bu yayının amacı, ortak dil ve anlayış birliğini sağlamak ve uluslar arası ticaretin daha hızlı, basit ve güvenli şekilde yürütülmesini gerçekleştirmektir.Türk hukuk sisteminde bu konuyu özel olarak düzenleyen bir yasa mevcut değildir. O yüzden uluslar arası ticaretle uğraşan kişilerin, vesaik mukabili ödeme yöntemini kullanarak ithalat-ihracat yapmak istediklerinde başvurabilecekleri kurallar URC 522 yayınıdır. Uluslararası ticarette taraflar URC 522 adıyla anılan yeknesak kuralların, kendi sözleşmelerine uygulanmasını sağlayabileceklerdir. Aksi durumda, yeknesak kurallar uygulanamayacaktır. Bu durumda, devletler özel hukuku kurallarına göre, söz konusu sözleşmeye uygulanacak hukukun tespiti gereklidir. Bu durumda ülkelerin milli hukuklarının, uluslar arası ticarete etkileri söz konusu olmaktadır. Yeknesak kuralların, kendiliğinden uygulanması söz konusu değildir.Uluslararası ticarette yeknesak kuralların varlığı olası problemleri en aza indirgemek açısından önemli ve gereklidir. One of the basic performances in international sale contract is payment. There are different types of payment methods in international trade law. Besides Letter of Credit Documents against payment? has an important place not only in Turkish export trade law but also in international business area.There is no current law arrangement about this payment method for all nations in international trade law. Therefore some organization have aimed to fill this legal loophole. One of this organizations is International Chamber of Commerce. This organization has aimed international trade to be tied with uniform rules. Therefore it has published some brochures. It has prepared and published Uniform Rules for Collections shortly called as URC 522 related documentary collections. Last revision was done in 1995. This brochure?s aim is to ensure common understanding and common language, and to be conducted more faster, guaranteed and easier of international trade.There are no special legal arrangement about this subject in Turkish legal system. Therefore, the actors who want to make export-import is mostly use the documents published in the brochure no URC 522.Parties of international trade can ensure application of the uniform rules called as URC 522 to their sales contracts. At the contrary case, uniform rules for collections is not applied. About this case, applicable law rules of Private International Law has to be determined to according contract. In such case, nations law regulations appear to effect in international trade. Uniform rules does not applicable per se.Existance of uniform rules in international trade is important and necessary for reducing possible problems.
Keywords: Akreditif; Alım-satım; Cash against documents; Commerce international; Commercial law; Contracts; International Chamber of Commerce; International Trade; International law; Letter of credit; Payment systems; Payments; Sale and purchase; Sözleşmeler; Terms of payment; Ticaret hukuku; Uluslararası Ticaret Odası; Uluslararası hukuk; Uluslararası ticaret; Vesaik mukabili ödeme; Ödeme sistemleri; Ödeme şekilleri; Ödemeler

The dilemma of national security and international cooperation in outer space: space technology trade and proliferation controls and their impact on global civil space cooperation - Mineiro, Michael (McGill University, 2011)
In this thesis space technology trade and proliferation controls are analyzed, focusing on two substantive issues that illustrate the challenges and opportunities of reform. The first substantive issue examined is the challenge of domestic law and policy reform in light of international regulatory divergence. This issue is examined through a case study of the U.S. commercial communication satellite export control regime. The second issue is the international implications of space technology trade and proliferation control on global civil space cooperation. The unifying demonstration of this doctoral thesis is that States operate in an international legal system that perpetuates a self-justified security dilemma whose basis originates in the sovereign legal right of States to produce, procure, and maintain space technologies of a military nature. As a result, the international legal system governing space technology trade and proliferation creates a tension between perceived national security needs and the benefits of global cooperation.

Market access and sustainable development: a legal policy analysis of the market access regime of the least developed countries under the WTO - Tania, Sharmin Jahan (Macquarie University, 2011)
"The main objective of the thesis is to examine whether improved market access for the exports of the least developed countries (LDCs) is a significant means for achieving sustainable development through trade. Further, it aims to examine whether LDCs face challenges in achieving their sustainable development in the existing market access regime... Recognising the specific needs of LDCs, the Preamble to the 'WTO Agreement' calls for positive efforts designed to ensure that LDCs secure a share in the growth in international trade commensurate with the needs of their economic development."
Keywords: Commerce; Developing countries; Exports; Foreign trade regulation; Free Trade; Sustainable development; WTO; World Trade Organization

Essays on policy reforms in trade, investment and taxation - Wagle, Swarnim (Australian National University, 2011)
This thesis consists of three essays on trade, investment, and taxation that are unified by their policy relevance to developing countries. Following an introductory chapter on policy reform, the first essay revisits the institutional determinants of foreign direct investment (FDI) using a comprehensive new data set covering more than 80 countries. It exploits the presence of confirmed zero investment flows between countries to estimate productivity cut-offs of firms that invest abroad profitably. This approach corrects likely biases arising from firm heterogeneity and country selection in a theoretically derived gravity-type model. The analysis finds inward FDI to be highly responsive to cross-country variation in specific institutional provisions, such as arbitration of disputes and legal procedures to establish foreign subsidiaries. The importance of FDI-specific regulations stands out even after controlling for the general quality of institutions. Statutory openness to FDI, however, has no association with actual inflow of investment. The second essay examines cross-national differences in the survival of exports through the lenses of product, industry, and country characteristics. The estimates are derived from a new application of discrete-time models instead of the continuous-time (Cox) models that are standard in trade duration analysis. The examination of exports originating in more than 100 developing countries covering 4000 products over 12 years shows that export flows are much more fragile than suggested by trade theory. Using new measures of product sophistication and export diversification, the paper finds evidence of information and network externalities that aid export survival. Exports concentrated in a few industries or in a narrow range of destination markets exhibit higher rates of death, whereas export concentration within some industries is positively associated with survival, suggesting a synergistic network effect. The probability of export death decreases with proximity from the capital content of products to the national factor endowment, competitive real exchange rate, and bilateral trade preferences. Further, death rates for dynamic subsets of exports like manufactured components and processed food differ from other products, belying the notion that short durations are necessarily a result of poor exporter capabilities. The third essay assesses the revenue implications of coordinated tariff and tax reforms. It is shown for a sample of low-income countries over 25 years that they have had a mixed record of offsetting reductions in trade tax revenue, and that Value-Added Tax (VAT) has, at best, played a limited role. The paper then analyzes the specific case of Nepal, using a unique data set compiled from unpublished customs records of imports, tariffs, and all other taxes levied at the border. It estimates changes to revenue and domestic production associated with two sets of reforms: i) proportional tariff cuts coordinated with a strictly enforced VAT; and ii) proposed tariff cuts under a regional free trade agreement. It is shown that a revenue-neutral tax reform is conditional on the effectiveness with which domestic taxes are enforced. Furthermore, loss of revenue as a result of intra-regional free trade can be minimized through judicious use of Sensitive Lists that still cover "substantially all the trade" as required by Article XXIV of the General Agreement on Tariffs and Trade (GATT).
Keywords: Commercial policy; Fiscal policy; Free Trade; Investments; Taxation

INCOTERMS as a form of standardisation in international sales law : an analysis of the interplay between mercantile custom and substantive sales law with specific reference to the passing of risk - Coetzee, Juana (University of Stellenbosch, 2010)
International sales contracts have very specific needs that stem from the multiplicity of legal systems which apply to such contracts. In addition to harmonised law, mercantile custom is able to address many of these needs. Mercantile custom represents usages which are clear, certain and efficient and are expected to be known and applied by merchants in a particular trade or region. To this extent mercantile custom fulfils an automatic harmonisation function. However, where a custom does not enjoy uniform application across all branches of trade, the harmonisation function of mercantile custom is limited, as is the case with trade terms. Trade terms reflect mercantile customs and usages which developed over a long time in order to simplify the trade in goods that are transported from one place to the other. They regulate the delivery obligations of the seller and buyer as well as associated obligations such as the passing of risk. Trade terms negate the need for elaborate contract clauses and appear in abbreviated form in contracts of sale. Although they provide a uniform expression of mercantile custom in a particular location or trade, the understanding of trade terms tend to differ from country to country, region to region or from one branch of trade to the next. The ICC INCOTERMS is an effort to standardise trade term definitions at the hand of the most consistent mercantile customs and practices. The aim of this study is to investigate the efficiency of INCOTERMS as a form of standardisation in international sales law. For purposes of the investigation the focus is limited to the passing of risk. Although national laws usually have a default risk regime in place, merchants still prefer to regulate risk by means of trade terms. This study will investigate the legal position in the case of FOB, CIF and DDU terms. An analysis of the risk regimes of a few selected national systems will show that each has their own understanding of these trade terms. The United Nations Convention on Contracts for the International Sale of Goods (CISG) does not refer to trade terms, but many commentators have concluded that the CISG risk rule is consistent with INCOTERMS. The study will discuss this in more detail. To determine the efficiency of INCOTERMS as a form of standardisation in international sales law, the study examines their characteristics, legal nature as well as their limited scope of regulation. Specific emphasis is placed on the interplay between the CISG and INCOTERMS and the possibility of some form of interaction and collaboration between the two instruments. It is concluded that collaboration between INCOTERMS and the CISG adds value to the international law of sales by increasing the efficiency of an international business transaction and thereby facilitating international trade.
Keywords: CISG; INCOTERMS; Mercantile custom; Standardisation

The participation of developing countries in the dispute settlement system of the WTO - Al. Shraideh, Saleh Adnan (Macquarie University, 2010)
International trade relations have become much more legalised under the World Trade Organization (WTO) than under the former international trade system created pursuant to the General Agreement on Tariffs and Trade (GATT). The Dispute Settlement Understanding (DSU) of the WTO clearly represents a shift toward a rule-oriented, legalistic and adjudicative approach, which is intended to enhance that status of, and confidence in, the WTO dispute settlement system. The approach is likely to ensure greater stability and predictability in the system by encouraging precise decisions on the merits of disputes and discouraging infractions. Its greater binding effect serves as a powerful disincentive to those Members who have a propensity to favour unilateral measures to solve international trade disputes. This is particularly beneficial for developing countries that sought a system which recognises their disadvantaged position compared to the greater bargaining and retaliatory power of developed countries. However, despite the positive assessment of the WTO dispute settlement system, the functioning of the system is working against the interest of developing countries in having an efficient dispute settlement system that considers their needs and deals fairly with their disputes. This thesis examines the participation of developing countries in the dispute settlement system of the WTO, and argues that they are in a disadvantageous position compared to their developed counterparts. The system's failure to effectively address or efficiently deal with this position is an evidence of its bias against and deficiency towards developing countries' participation. The thesis focuses on the problematic issues developing countries face throughout their use of the system. It also considers the role that the DSU has played in addressing these issues and the efficiency of that role in restraining and limiting their effect on developing countries' participation in the system. The thesis analyses some ideas on the reform of the DSU that have been proposed through WTO negotiations or literature, and discusses their applicability on the current dispute settlement system. Finally, the thesis employs these proposals along with its discussion on the subject to introduce a reformed model of the DSU which is more sensitive to developing countries' concerns in the system in order to help providing an understanding of how such modifications could be carried out in future reforms on the DSU.
Keywords: Conflict management; Developing countries; Foreign economic relations; GATT; General Agreement on Tariffs and Trade; International relations; Politics and government; WTO; World Trade Organization